Polymer, tackifier, adhesive composition, adhesive sheet, optical laminate, and image display device
Patent Information
- Application Number
- CN202580020533.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-19
- Filing Date
- 2025-03-17
- Publication Date
- 2026-10-13
AI Technical Summary
[0028]根据本发明的实施方式,能够提供可以在粘合剂组合物中使用、并且适合用于光学层叠体、图像显示装置、同时适合制造粘接力得到了改善的粘合片的聚合物。
Smart Images

Figure CN122910259A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to polymers, tackifiers, adhesive compositions, adhesive sheets, optical laminates, and image display devices. Background Technology
[0002] In recent years, image display devices, represented by liquid crystal displays and electroluminescent (EL) displays (e.g., organic EL displays and inorganic EL displays), have become increasingly widespread. Image display devices generally comprise an optical laminate containing optical substrates such as polarizing films and retardation films. In an optical laminate containing multiple optical substrates, a bonding layer is typically disposed between adjacent optical substrates to join them together. One example of a bonding layer is an adhesive sheet formed from an adhesive composition.
[0003] Patent Document 1 discloses an example of an adhesive sheet. In Patent Document 1, the adhesive sheet is made from a thermosetting adhesive composition. In addition to thermosetting adhesive compositions, light-curing adhesive compositions capable of producing adhesive sheets using light are also known.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-14376 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] To improve the surface brightness of an image display device, it is advantageous to use an adhesive sheet with a high refractive index. However, according to the research of the inventors, there is room for improvement in the adhesive strength of adhesive sheets with high refractive indexes.
[0009] The object of the present invention is to provide a polymer that can be used in adhesive compositions and is suitable for use in optical laminates, image display devices, and is also suitable for manufacturing adhesive sheets with improved adhesion.
[0010] Problem Solving Methods
[0011] [1] The polymers of the embodiments of the present invention have a weight-average molecular weight of 1,500 to 30,000, a glass transition temperature of 30°C or less, and a refractive index of 1.51 or more.
[0012] [2] The δH of the polymer described in [1] above can be below 5.15. Wherein, the above δH is the hydrogen bond term of the Hansen solubility parameter (HSP).
[0013] [3] The colorimetric properties of the polymer described in [1] or [2] above are as specified in CIE 1976 L as defined in JIS Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value can be less than 1.1.
[0014] [4] The weight-average molecular weight of the polymer described in any one of [1] to [3] above can be 2400 to 16000.
[0015] [5] The polymer described in any one of [1] to [4] above may contain a constituent unit derived from a monomer b having a double bond ring.
[0016] [6] In the polymer described above [5], the double-bonded ring can be an aromatic ring.
[0017] [7] In the polymers described in [5] or [6] above, the monomer b may have two or more of the double-bonded rings in the side chain.
[0018] [8] In any of the polymers described in [5] to [7] above, the monomer b may have a structure in which the first double-bonded ring and the second double-bonded ring contained in the two or more double-bonded rings are bonded together by a linking group in the side chain.
[0019] [9] In any of the polymers described in any of [5] to [8] above, the monomer b may be phenoxybenzyl acrylate.
[0020]
[10] The content of the constituent unit derived from the monomer b in the polymer described in any one of [5] to [9] above may be 50% by weight or more.
[0021]
[11] The tackifier of the embodiments of the present invention comprises any one of the polymers described in [1] to
[10] above.
[0022]
[12] The tackifier of the present invention comprises a polymer having a weight average molecular weight of 1,500 to 30,000, wherein the polymer comprises a constituent unit derived from a monomer b having a double-bonded ring, wherein the monomer b has two or more of the double-bonded rings in the side chain.
[0023]
[13] The adhesive composition of the embodiments of the present invention is a light-curing adhesive composition comprising monomer component M and the polymer described in any one of [1] to
[10] above or the tackifier described in
[11] or
[12] above.
[0024]
[14] The adhesive sheet of the embodiment of the present invention is an adhesive sheet formed from the adhesive composition described above
[13] .
[0025]
[15] The optical laminate of the present invention comprises the adhesive sheet and the optical film described in
[14] above.
[0026]
[16] The image display device according to the embodiments of the present invention includes the optical laminate described above
[15] .
[0027] The effects of the invention
[0028] According to embodiments of the present invention, it is possible to provide polymers that can be used in adhesive compositions and are suitable for use in optical laminates, image display devices, and are also suitable for manufacturing adhesive sheets with improved adhesion. Attached Figure Description
[0029] Figure 1 This is a simplified cross-sectional view of an adhesive sheet according to one embodiment of the present invention.
[0030] Figure 2 This is a schematic diagram illustrating an example of a method for forming an adhesive sheet from the adhesive composition of the present invention.
[0031] Figure 3 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0032] Figure 4 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0033] Figure 5 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0034] Figure 6 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0035] Figure 7 This is a simplified cross-sectional view of an image display device according to one embodiment of the present invention. Detailed Implementation
[0036] [Regarding terminology]
[0037] In this specification, the use of the term "weight" can be interpreted as "mass," which is the SI unit conventionally used to represent weight. The reverse is also true.
[0038] In this specification, the term "(meth)acrylic acid" refers to "acrylic acid and / or methacrylic acid", the term "(meth)acrylate" refers to "acrylate and / or methacrylate", the term "(meth)allyl" refers to "allyl and / or methylallyl", and the term "(meth)acrolein" refers to "acrolein and / or methacrolein".
[0039] In this specification, when “100 parts by weight of monomeric component M” is described as a basis for the content of various components in the adhesive composition, it refers to the total amount of monomeric component M contained in the adhesive composition that has not undergone partial polymerization and monomeric component M consumed in the formation of some polymers that may be contained in the adhesive composition.
[0040] In this specification, when “100 parts by weight of monomeric component M and inorganic particles” is described as a basis for the content of various components in the adhesive composition, it refers to the total amount of monomeric component M that has not undergone partial polymerization, monomeric component M consumed in the formation of some polymers that may be contained in the adhesive composition, and inorganic particles.
[0041] 《1. Polymer B》
[0042] The polymer of the present invention (hereinafter referred to as "polymer B") has (I) a weight-average molecular weight of 1,500 to 30,000, (II) a glass transition temperature of 30°C or less, and (III) a refractive index of 1.51 or more. Polymer B can be used, for example, as an additive in adhesive compositions.
[0043] 1-1. Properties of Polymer B
[0044] <1-1-a. Weight-average molecular weight>
[0045] Polymer B has a weight-average molecular weight (hereinafter referred to as "Mw") of 1500 to 30000. A Mw of 1500 to 30000 helps improve the adhesive strength of the adhesive sheet. Furthermore, a Mw of 1500 to 30000 also contributes to improved compatibility with the adhesive composition and, consequently, ensures the optical properties of the adhesive sheet, such as the suppression of haze increase due to the addition of polymer B. Adhesive sheets with suppressed haze are suitable for use in optical laminates and image display devices.
[0046] Mw can be below 25,000, or below 20,000, 18,000, 16,000, 15,000, 13,000, 10,000, 8,000, and even below 6,000. Mw can be above 1,500, or above 2,000, 2,400, 2,500, 3,000, 3,500, and even above 4,000. Mw can be between 2,000 and 16,000, or between 2,400 and 16,000, and even between 4,000 and 16,000.
[0047] The Mw of polymer B can be determined using GPC (gel permeation chromatography) in the form of a polystyrene equivalent. However, it should be noted that when evaluating the properties described in this specification, represented by Mw, the solvent content in polymer B must be reduced to less than 0.1% by weight beforehand through thorough drying. Drying can be achieved using heating, reduced pressure, or electromagnetic wave irradiation.
[0048] <1-1-b. Glass transition temperature>
[0049] Polymer B has a glass transition temperature (hereinafter referred to as "Tg") below 30°C. A Tg below 30°C can help improve the adhesive strength of the adhesive sheet. In addition, a Tg below 30°C can also help improve the compatibility with the adhesive composition and thus ensure the optical properties of the adhesive sheet, such as the suppression of haze increase due to the addition of polymer B.
[0050] Temperature (Tg) can be below 50°C, below 45°C, below 40°C, below 35°C, below 30°C, below 25°C, below 20°C, below 15°C, below 10°C, below 8°C, below 5°C, below 2°C, below 1°C, below 0°C, below -1°C, below -2°C, below -3°C, below -4°C, below -5°C, and further below -6°C. The lower limit of Tg, for example, above -50°C, can be above -45°C, above -40°C, above -35°C, above -30°C, above -25°C, above -20°C, above -15°C, and further above -10°C.
[0051] The Tg of polymer B can be determined by differential scanning calorimetry (DSC). The specific measurement method is as follows. First, prepare the analyte (polymer B) and reference material (standard material) sealed in an aluminum sample pan. Next, perform DSC measurement of the analyte using a differential scanning calorimeter (e.g., TA INSTRUMENTS Q2000). Perform three cycles of measurement, setting the heating and cooling rates to 10°C / min. Furthermore, the measurement is performed within a range of at least ±70°C, using the temperature at which the baseline shift occurs as a reference. During the heating process in each cycle, determine the temperature at the midpoint between the inflection point on the low-temperature side and the inflection point on the high-temperature side of the baseline shift; this temperature is taken as the Tg of the analyte measured in each cycle. The average of the above Tg values from the second and third cycles is determined as the Tg of polymer B.
[0052] <1-1-c. Refractive Index>
[0053] Polymer B has a refractive index of 1.51 or higher. A refractive index of 1.51 or higher can help improve the refractive index of the adhesive sheet. In addition, a refractive index of 1.51 or higher can also help ensure the optical properties of the adhesive sheet, such as suppressing the increase of haze due to the addition of polymer B to the adhesive composition with a high refractive index.
[0054] The refractive index can be 1.52 or higher, 1.53 or higher, 1.54 or higher, 1.55 or higher, 1.56 or higher, 1.57 or higher, 1.58 or higher, 1.59 or higher, and further up to 1.595 or higher. The upper limit of the refractive index is, for example, below 3.00, and can be below 2.50, below 2.00, below 1.90, below 1.80, below 1.70, below 1.69, below 1.68, below 1.67, below 1.66, below 1.65, below 1.64, below 1.63, below 1.62, below 1.61, and further down to below 1.60.
[0055] The refractive index of polymer B can be measured using an Abbe refractometer at a measurement wavelength of 589 nm and a measurement temperature of 25°C. An Abbe refractometer, such as the ATAGO DR-M4 or its equivalent (e.g., DR-M2), can be used. It should be noted that, for the sample used to evaluate polymer B, as described above, the solvent content is reduced to less than 0.1% through vacuum drying or similar methods. The sample is dropped onto a smooth glass substrate to create a laminate of glass and polymer B, and the surface of polymer B is brought into contact with the prism, which serves as the measuring part of the Abbe refractometer. The sample is then left at room temperature for approximately 10 minutes to achieve a clearly defined interface between the prism and polymer B, and the measurement is performed at 25°C. If the Tg of polymer B is high and it is difficult to clearly form an interface between the prism and polymer B, the interface can be formed by heating to approximately 50°C. In this case, the measurement is performed after the temperature returns to 25°C.
[0056] <1-1-d. Hansen's solubility parameter (HSP)>
[0057] The δH of polymer B can be below 5.15. Here, δH is the hydrogen bonding term of the Hansen solubility parameter (HSP). When δH is suppressed to below 5.15, it can help suppress gelation when forming adhesive sheets from adhesive compositions containing polymer B.
[0058] δH can be below 5.10, below 5.05, below 5.00, below 4.95, below 4.90, below 4.85, below 4.80, below 4.75, below 4.70, and further below 4.65. The lower limit of δH is, for example, above 3.70, and can be above 3.80, above 3.90, above 4.00, above 4.10, above 4.20, and further above 4.30.
[0059] The Hansen solubility parameter (HSP) is a parameter derived by breaking down the solubility parameter proposed by Hildebrand into three components: dispersion term δD, polar term δP, and hydrogen bonding term δH. δD represents the energy of the dispersion forces between molecules. δP represents the energy of the polar forces between molecules. δH represents the energy of the hydrogen bonding forces between molecules. The unit for each component is typically MPa. 1 / 2The three components described above can be used to determine a point (vector) in a known three-dimensional space, which is the Hansen space. Details of the Hansen solubility parameters are disclosed in "Hansen Solubility Parameters; A User's Handbook (CRC Press, 2007)". The δD, δP, and δH of polymer B can be determined, for example, using known software such as HSPiP (version 5), based on the constituent units of polymer B and the content of those units in polymer B, and through calculation. More specifically, the δD, δP, and δH of each constituent unit can be calculated separately, and the weighted average obtained by weighting the calculated δD, δP, and δH by the content of that unit is taken as the δD, δP, and δH of polymer B. The calculation is performed at a temperature of 23°C.
[0060] The δP of polymer B can be 3.15 or higher, or 3.20 or higher, 3.30 or higher, 3.40 or higher, 3.50 or higher, 3.60 or higher, 3.70 or higher, and further, 3.80 or higher. The upper limit of δP is, for example, 5.00 or lower, and can be 4.90 or lower, 4.80 or lower, 4.70 or lower, 4.60 or lower, 4.50 or lower, 4.40 or lower, 4.30 or lower, 4.20 or lower, 4.10 or lower, 4.00 or lower, and further, 3.90 or lower. As mentioned above, δP is the polar term of HSP.
[0061] The δD of polymer B can be 17.85 or higher, or 17.90 or higher, 18.00 or higher, 18.10 or higher, 18.20 or higher, 18.30 or higher, 18.40 or higher, 18.50 or higher, 18.60 or higher, and further, 18.65 or higher. The upper limit of δD is, for example, below 20.00, and can be below 19.75, below 19.50, below 19.25, below 19.00, below 18.90, and further, below 18.80 or below 18.70.
[0062] <1-1-e. Chromaticity>
[0063] The colorimetric properties of polymer B are as specified in CIE 1976 L as defined in Japanese Industrial Standard (JIS) Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value of can be below 1.1. Chromaticity The absolute value can be below 1.0, below 0.9, below 0.8, below 0.7, below 0.6, below 0.5, below 0.4, and even below 0.3. (Color intensity) The lower limit of the absolute value is 0 (zero), and it can be greater than 0.05, greater than 0.1, and even greater than 0.2.
[0064] The chromaticity of polymer B can be determined as follows. First, prepare two alkali-free glass plates (thickness 0.7~0.8mm, total light transmittance 92%, chromaticity...). 0.20). Next, a polyimide tape (50 μm thick) is attached in a frame shape to one side of an alkali-free glass plate. This attachment creates an area on the aforementioned single side surrounded by the polyimide tape. Next, the polymer B being evaluated is heated to a flowable state, and an appropriate amount is placed in the aforementioned area. Next, polymer B is stretched using another alkali-free glass plate, creating a 50 μm thick sheet of polymer B sandwiched between the two alkali-free glass plates. After cooling the sheet to room temperature, the transmittance of the sheet for light with wavelengths from 300 nm to 800 nm is measured in a 23°C environment using an analytical device such as a spectrophotometer (e.g., a Hitachi High-Tech UV-Vis-NIR spectrophotometer UH4150). Based on the spectral data obtained through measurement, the chromaticity can be determined using analytical software (e.g., Hitachi High-Tech's UV Solutions color calculation program). The absolute value. It should be noted that determining chromaticity... When the absolute value is used, the reference data (blank data) measured without the sample being placed in the analytical apparatus is used as the benchmark.
[0065] 1-2. Composition of Polymer B
[0066] <1-2-a. Monomers with double-bonded rings b>
[0067] Preferred polymer B comprises a building block derived from monomer b having a double-bonded ring. Polymer B comprising building blocks derived from monomer b can help improve the refractive index of the adhesive sheet. Polymer B may comprise one or more building blocks derived from monomer b.
[0068] In this specification, a double-bonded ring refers to a ring in which at least one of the bonds constituting the ring is a double bond. Examples of double bonds include carbon-carbon double bonds, carbon-heteroatom double bonds, and heteroatom-heteroatom double bonds. Examples of heteroatoms include nitrogen, sulfur, and oxygen.
[0069] The number of double bonds in a double-bonded ring is not particularly limited, for example, it can be 1 to 10, or 2 to 5. When a double-bonded ring contains more than two double bonds, these double bonds can be conjugated or non-conjugated. The double-bonded ring is preferably an aromatic ring.
[0070] The ring containing the double bond can be a carbon ring. Examples of carbon rings include benzene rings (which can be benzene rings that form part of biphenyl or fluorene structures), naphthalene rings, and indene rings. Rings, anthracene rings, and phenanthrene rings. Rings containing double bonds can also be heterocycles. Examples of heterocycles include pyridine rings, pyrimidine rings, pyridazine rings, pyrazine rings, triazine rings, pyrrole rings, pyrazole rings, imidazole rings, and triazole rings. azole ring, iso- Azazole ring, thiazole ring, and thiophene ring. Examples of heteroatoms that can be included in a heterocycle as cyclic atoms are at least one selected from nitrogen, sulfur, and oxygen. The heteroatom can be one or both of nitrogen and sulfur. The ring containing the double bond can be a fused ring. An example of monomer b is a structure like the dinaphthothiophene structure, which has one or more carbon rings fused with one or more heterocycles.
[0071] The double-bonded ring may have one or more substituents (except for the olefinic unsaturated groups described later) on the cyclizing atom, or it may not have substituents. Examples of substituents are alkyl, alkoxy, aryloxy, hydroxyl, halogen atoms (fluorine, chlorine, bromine, etc.), hydroxyalkyl, hydroxyalkoxy, and glycidoxy. However, the substituents are not limited to the above examples. The substituents may also contain carbon atoms, in which case the number of carbon atoms contained in the substituent is, for example, 1 to 4, 1 to 3, and further, 1 to 2. One example of a double-bonded ring is that the cyclizing atom does not have a substituent. Another example of a double-bonded ring is that the cyclizing atom has one or more substituents selected from alkyl, alkoxy, and halogen atoms (e.g., bromine).
[0072] In monomer b, the number of double-bonded rings contained in one molecule can be, for example, 1, or more than 2. There is no particular upper limit to the number of double-bonded rings, for example, 16 or less. The upper limit can be less than 12, less than 8, less than 6, less than 5, less than 4, less than 3, and further less than 2.
[0073] In monomer b, the double-bonded ring is preferably located in the side chain. In other words, monomer b preferably has at least one double-bonded ring and at least one olefinically unsaturated group in one molecule. As monomer b, it is preferable to use a compound that contains one olefinically unsaturated group in one molecule (in other words, a monofunctional monomer). Monomer b may have two or more double-bonded rings in its side chain.
[0074] Monomer b can have a structure in which the first and second double-bonded rings in a side chain are bonded together via linking groups. Polymer B containing constituent units derived from monomer b having this structure in its side chain tends to be less prone to crystallization. If crystallization does occur, it will hinder the mixing of polymer B into the adhesive composition.
[0075] The linking group that exists between the first and second double-bonded rings can contain atoms such as P, Ge, Te, Se, N, S, and Si, which can be bonded to oxygen atoms. However, the linking group may also not contain the aforementioned atoms. Examples of linking groups are oxy groups (-O-), thiooxy groups (-S-), and oxoalkylene groups (e.g., -O-(CH2)). n -; n is 1~3, preferably 1), thionyl groups (e.g., -S-(CH2) n -; n is 1~3, preferably 1), straight-chain alkylene (-(CH2) n - (n is 1 to 6, preferably 1 to 3), and groups formed by partial or complete halogenation of the above-mentioned oxoalkylene, thioalkylene, and straight-chain alkylene groups. The linking group may contain one or more selected from oxygen, thiooxy, oxoalkylene, and straight-chain alkylene groups. The linking group may contain an oxygen group.
[0076] Examples of olefinically unsaturated groups are (meth)acryloyl, vinyl, and (meth)allyl. From the viewpoint of polymerization reactivity, (meth)acryloyl is preferred, and from the viewpoint of flexibility and adhesiveness, acryloyl is more preferred. In other words, monomer b preferably comprises a (meth)acrylic acid monomer having a double-bonded ring, and more preferably comprises an acrylic acid monomer containing a double-bonded ring. Examples of (meth)acrylic acid monomers having a double-bonded ring include, for example, aromatic ring (meth)acrylates. Specific examples of aromatic ring (meth)acrylates will be described later.
[0077] The double-bonded ring and the olefinic unsaturated group can be directly bonded or bonded via a linking group. One example of a linking group that may exist between the double-bonded ring and the olefinic unsaturated group is a group selected from alkylene, oxoalkylene, poly(olefinic oxide), phenyl, alkylphenyl, alkoxyphenyl, groups in which one or more hydrogen atoms are replaced by hydroxyl groups (e.g., hydroxyalkylene), oxy (-O-), and thiooxy (-S-). In one example of monomer b, the double-bonded ring and the olefinic unsaturated group are directly bonded together. In another example of monomer b, the double-bonded ring and the olefinic unsaturated group are bonded together via a linking group selected from alkylene, oxoalkylene, and poly(olefinic oxide). The number of carbon atoms in the alkylene and oxoalkylene groups that may be included in the linking group is, for example, 1 to 4, 1 to 3, and further, 1 to 2. The number of repeating olefin units in the poly(olefin oxide) group that may be included in the linking group is, for example, 1 to 8, 1 to 6, 1 to 4, 1 to 3, 2 to 3, and further, 1 to 2, 2, or 1.
[0078] Specific examples of monomer b are aromatic ring (meth)acrylates and aromatic ring vinyl compounds. One or more aromatic ring (meth)acrylates and aromatic ring vinyl compounds may be used.
[0079] Monomer b may contain two or more aromatic rings (preferably carbocyclic rings) in one molecule. Monomers having two or more aromatic rings and at least one olefinic unsaturated group in one molecule (monomers containing multiple aromatic rings) are particularly suitable for increasing the refractive index of the adhesive sheet. The two or more aromatic rings may be located on the side chain of monomer b.
[0080] Examples of monomers containing multiple aromatic rings include: monomers having a structure in which two or more non-fused aromatic rings are bonded together via a linking group; monomers having a structure in which two or more non-fused aromatic rings are directly bonded together; monomers having fused rings; monomers having a fluorene structure; monomers having a dinaphthothiophene structure; and monomers having a dibenzothiophene structure. Monomers containing multiple aromatic rings may have the above-described structures in their side chains. Preferably, monomers having a structure in which two or more non-fused aromatic rings are bonded together via a linking group in their side chains (e.g., phenoxybenzyl (meth)acrylate described later) are used.
[0081] Examples of linking groups that can exist between two or more non-fused aromatic rings are the same as examples of linking groups that can exist between a first double-bonded ring and a second double-bonded ring.
[0082] Examples of monomers having a structure formed by the direct bonding of two or more non-fused aromatic rings include (meth)acrylates containing a biphenyl structure, (meth)acrylates containing a triphenyl structure, and monomers containing vinylbiphenyl. Specific examples include o-phenylphenol (meth)acrylate, biphenyl (meth)acrylate, and biphenyl methyl (meth)acrylate.
[0083] Examples of monomers with fused rings include naphthyl ring (meth)acrylates, anthracene ring (meth)acrylates, acetylnaphthalene, and acetylanthracene. Specific examples include 1-naphthyl methyl (meth)acrylate (also known as 1-naphthyl methyl (meth)acrylate), hydroxyethylated β-naphthol acrylate, 2-naphthyl ethyl (meth)acrylate, 2-naphthoxyethyl acrylate, and 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate.
[0084] Examples of monomers having a fluorene structure are 9,9-bis(4-hydroxyphenyl)fluorene(meth)acrylate and 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene(meth)acrylate. It should be noted that monomers having a fluorene structure are included in the concept of monomers having structures formed by the direct bonding of two benzene rings, since they possess a structure formed by the direct bonding of two or more non-fused aromatic rings.
[0085] Examples of monomers having a dinaphthothiophene structure are dinaphthothiophene containing a (meth)acryloyl group, dinaphthothiophene containing an acetyl group, and dinaphthothiophene containing a (meth)allyl group. Specific examples include (meth)acryloyloxymethyl dinaphthothiophene (e.g., a compound having a structure in which a CH2CH(R1)C(O)OCH2 group is bonded at the 5 or 6 position of the dinaphthothiophene ring; R1 being a hydrogen atom or a methyl group), (meth)acryloyloxyethyl dinaphthothiophene (e.g., a compound having a CH2CH(R1)C(O)OCH(CH3) group or a CH2CH(R1)C(O)OCH2CH2 group is bonded at the 5 or 6 position of the dinaphthothiophene ring; R1 being a hydrogen atom or a methyl group), vinyl dinaphthothiophene (e.g., a compound having a structure in which a vinyl group is bonded at the 5 or 6 position of the dinaphthothiophene ring), and (meth)allyloxy dinaphthothiophene. It should be noted that monomers with a dinaphthothiophene structure are included in the concept of monomers with fused rings because they have a naphthalene structure, and also because they have a structure formed by the fusion of a thiophene ring and two naphthalene structures.
[0086] Examples of monomers having a dibenzothiophene structure include dibenzothiophene containing a (meth)acryloyl group and dibenzothiophene containing an acetyl group. It should be noted that monomers having a dibenzothiophene structure are included in the concept of monomers with fused rings because they possess a structure formed by the fusion of a thiophene ring and two benzene rings. Neither dinaphthothiophene nor dibenzothiophene structures belong to structures formed by the direct bonding of two or more non-fused aromatic rings.
[0087] Monomer b can be a monomer (containing a single aromatic ring monomer) having an aromatic ring (preferably a carbocyclic ring) and at least one olefinic unsaturated group in one molecule.
[0088] Examples of monomers containing a single aromatic ring include benzyl (meth)acrylate, methoxybenzyl (meth)acrylate, phenyl (meth)acrylate, ethoxylated phenol (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxybutyl (meth)acrylate, cresol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, benzyl chloro (meth)acrylate, and other (meth)acrylates containing a carbon aromatic ring; 2-(4,6-dibromo-2-sec-butylphenoxy)ethyl (meth)acrylate, 2-(4,6-dibromo-2-isopropylphenoxy)acrylate, etc. methyl methacrylates containing bromine-substituted aromatic rings, such as 6-(4,6-dibromo-2-sec-butylphenoxy)hexyl methacrylate, 6-(4,6-dibromo-2-isopropylphenoxy)hexyl methacrylate, 2,6-dibromo-4-nonylphenyl acrylate, and 2,6-dibromo-4-dodecylphenyl acrylate; vinyl compounds containing carbon aromatic rings, such as styrene, α-methylstyrene, vinyltoluene, and tert-butylstyrene; N-vinylpyridine, N-vinylpyrimidine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazolium, and N-vinylpyrrolidone. Compounds such as azoles that have vinyl substituents on heteroaromatic rings.
[0089] Monomer b can have a structure in which an oxyethylidene chain is sandwiched between the olefinic unsaturated group and the double-bonded ring in the various monomers b described above. Monomers having this structure can be considered ethoxylated versions of the original monomer. The number of repetitions of the oxyethylidene unit (-CH2CH2O-) in the oxyethylidene chain is, for example, 1 to 8, but can be 1 to 6, 1 to 4, 1 to 3, further 1 to 2, or even 1. Examples of monomer b as ethoxylated versions are ethoxylated o-phenylphenol (meth)acrylate, ethoxylated nonylphenol (meth)acrylate, ethoxylated cresol (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxydiethylene glycol (meth)acrylate.
[0090] Monomer b may include high-refractive-index monomers. In this specification, a high-refractive-index monomer refers to a monomer having a refractive index of 1.51 or higher, 1.53 or higher, 1.55 or higher, 1.56 or higher, 1.57 or higher, 1.58 or higher, 1.59 or higher, 1.60 or higher, 1.61 or higher, 1.62 or higher, 1.63 or higher, 1.64 or higher, 1.65 or higher, 1.66 or higher, 1.67 or higher, 1.68 or higher, and further, 1.69 or higher. There is no particular upper limit to the refractive index of the high-refractive-index monomer; for example, it can be below 3.00, below 2.50, below 2.00, below 1.90, below 1.80, and further, below 1.70. A single high-refractive-index monomer may be used, or two or more may be used in combination.
[0091] The refractive index of the monomer can be measured using an Abbe refractometer at a measurement wavelength of 589 nm and a measurement temperature of 25°C. An Abbe refractometer, such as the ATAGO DR-M4 or its equivalent (e.g., DR-M2), can be used. If the monomer manufacturer provides a nominal value for the refractive index at 25°C, that value can be used as the refractive index.
[0092] Examples of high-refractive-index monomers include phenoxybenzyl acrylate (refractive index 1.566), 1-naphthyl methyl acrylate (refractive index 1.595), ethoxylated o-phenylphenol acrylate (refractive index 1.578 when the repeating number of the oxyethylidene unit is 1), benzyl acrylate (refractive index 1.519), phenoxyethyl acrylate (refractive index 1.517), phenoxydiethylene glycol acrylate (refractive index 1.510), 6-acryloyloxymethyl dinaphthothiophene (refractive index 1.75), 6-methacryloyloxymethyl dinaphthothiophene (refractive index 1.726), 5-acryloyloxyethyl dinaphthothiophene (refractive index 1.786), 6-acryloyloxyethyl dinaphthothiophene (refractive index 1.722), 6-vinyl dinaphthothiophene (refractive index 1.802), and 5-vinyl dinaphthothiophene (refractive index 1.793). However, high-refractive-index monomers are not limited to the examples mentioned above. Monomer b preferably contains phenoxybenzyl acrylate as a high refractive index monomer.
[0093] The content of constituent units derived from monomer b in polymer B is, for example, 10% by weight or more, and can be 30% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 98% by weight or more, 99% by weight or more, and further, 100% by weight. The above content may, depending on the circumstances, be less than 10% by weight, less than 5% by weight, and further, less than 1% by weight. Polymer B may also not contain constituent units derived from monomer b.
[0094] <1-2-b. Other monomers>
[0095] Polymer B may contain building blocks derived from monomer c other than monomer b. An example of monomer c is a hydroxyl-containing monomer. A hydroxyl-containing monomer has at least one hydroxyl group and at least one olefinically unsaturated group in one molecule. Polymer B may contain one or more building blocks derived from hydroxyl-containing monomers.
[0096] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer b. Hydroxyl-containing monomers can be (meth)acrylic acid monomers.
[0097] Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylaurate (meth)acrylate, and methyl (4-hydroxymethylcyclohexyl)acrylate. 4-hydroxybutyl (meth)acrylate is preferred.
[0098] The content of constituent units derived from hydroxyl-containing monomers in polymer B is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, less than 5% by weight, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, and further, 0.5% by weight or more. Polymer B may also not contain constituent units derived from hydroxyl-containing monomers.
[0099] Polymer B contains constituent units derived from hydroxyl-containing monomers. The content of constituent units derived from hydroxyl-containing monomers in polymer B can be less than 5% by weight, or less than 4% by weight, less than 3% by weight, less than 2% by weight, or even less than 1% by weight.
[0100] Another example of monomer c is an alkyl (meth)acrylate having an alkyl group having 1 to 20 carbon atoms in its side chain. The alkyl group may have 7 or fewer carbon atoms, 6 or fewer, 5 or fewer, or even 4 or fewer. The alkyl group may be linear or branched. Polymer B may contain one or more constituent units derived from alkyl (meth)acrylates.
[0101] Examples of alkyl methacrylates are methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, isoheptyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, n-dodecyl methacrylate (laurate methacrylate), n-tridecyl methacrylate, n-tetradecyl methacrylate, n-pentadecanyl methacrylate, n-hexadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate, and octadecyl methacrylate. Alkyl methacrylates can be n-butyl methacrylates.
[0102] The content of (meth)acrylate-derived constituent units in polymer B is, for example, 50% by weight or less, and can be 40% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, and further, 4% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. The lower limit of the content may be 50% by weight or more, depending on the circumstances. Polymer B may also not contain constituent units derived from (meth)acrylate.
[0103] Another example of monomer c is an aliphatic ring monomer. An aliphatic ring monomer has at least one aliphatic ring and at least one olefinically unsaturated group in one molecule. Polymer B may contain one or more building blocks derived from aliphatic ring monomers.
[0104] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer b. Monomers containing aliphatic rings can be (meth)acrylic acid monomers.
[0105] Examples of aliphatic ring monomers include: cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, dicyclopentoxyethyl methacrylate, tricyclopentyl methacrylate, and adamantyl methacrylate.
[0106] The content of constituent units derived from aliphatic ring monomers in polymer B is, for example, 50% by weight or less, but can be 40% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, and further, 2% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. The lower limit of the content may, depending on the circumstances, be 50% by weight or more, 80% by weight or more, and further, 90% by weight or more. Polymer B may also not contain constituent units derived from aliphatic ring monomers.
[0107] Polymer B may contain building blocks derived from monomers having acidic groups. Another example of monomer c is a carboxyl-containing monomer. A carboxyl-containing monomer has at least one carboxyl group and at least one olefinically unsaturated group in one molecule. Monomer component M may contain one or more carboxyl-containing monomers. Polymer B may contain one or more building blocks derived from carboxyl-containing monomers.
[0108] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer b. The carboxyl-containing monomer can be a (meth)acrylic acid monomer.
[0109] The content of carboxyl-containing monomer-derived constituent units in polymer B is, for example, 10% by weight or less, and can be 7% by weight or less, 5% by weight or less, 3% by weight or less, or even 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, or even 1% by weight or more. Polymer B preferably does not contain constituent units derived from carboxyl-containing monomers.
[0110] Polymer B contains building blocks derived from carboxyl-containing monomers, and the percentage of building blocks derived from carboxyl-containing monomers in polymer B may be less than 1% by weight.
[0111] Another example of monomer c is a nitrogen-containing monomer. A nitrogen-containing monomer is a monomer that has at least one nitrogen atom within a molecule (within one molecule).
[0112] Examples of nitrogen-containing monomers include N-vinyl cyclic amides and (meth)acrylamide. Polymer B may contain one or more building blocks derived from nitrogen-containing monomers.
[0113] Examples of N-vinylcyclic amides include N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidinone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, and N-vinyl-1,3- Azin-2-one, N-vinyl-3,5-morpholinidone, vinylmethyl Examples include azole ketones. As (meth)acrylamides, examples include (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. (Methacrylamides) also include various N-hydroxyalkyl (meth)acrylamides and N-alkoxyalkyl (meth)acrylamides.
[0114] Examples of nitrogen-containing monomers other than N-vinylcyclic amides and (meth)acrylamide include aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; cyano monomers such as acrylonitrile and methacrylonitrile; and monomers such as (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazolium, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, and vinyl... azole, vinylisothion Heterocyclic monomers such as azoles, vinylthiazoles, vinylisothiazoles, vinylpyridazines, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, and N-methylvinylpyrrolidone; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, and N-octylitaconimide. Itaconitum monomers such as itaconitum, N-2-ethylhexyl itaconitum, N-lauryl itaconitum, and N-cyclohexyl itaconitum; succinimide monomers containing imide groups, such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxohexamethylenesuccinimide, and N-(meth)acryloyl-8-oxooctamethylenesuccinimide; and isocyanate-containing monomers, such as 2-(meth)acryloyloxyethyl isocyanate.
[0115] The content of nitrogen-containing monomers in polymer B is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, and further, 0.5% by weight or more. Polymer B may also not contain any nitrogen-containing monomers.
[0116] Another example of monomer c is an ether-containing monomer. An ether-containing monomer has at least one ether group and at least one olefinically unsaturated group in one molecule. Polymer B may contain one or more building blocks derived from ether-containing monomers.
[0117] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer b. Ether-containing monomers can be (meth)acrylic acid monomers.
[0118] Examples of ether-containing monomers are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxydipropylene glycol (meth)acrylate. The preferred ether-containing monomer is 2-(2-ethoxyethoxy)ethyl acrylate (CBA).
[0119] The content of constituent units derived from ether-containing monomers in polymer B is, for example, 40% by weight or less, but can be 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, and further, 0.5% by weight or more. Polymer B may also not contain constituent units derived from ether-containing monomers.
[0120] 1-3. Preparation method of polymer B
[0121] Polymer B can be produced using known polymerization methods such as solution polymerization, radiation polymerization, bulk polymerization, emulsion polymerization, and polymerization under supercritical conditions, including free radical polymerization. Examples of radiation that can be used in radiation polymerization include electron beams, UV radiation, and microwaves. The resulting polymer B can be any copolymer, such as random copolymers, block copolymers, or graft copolymers.
[0122] 1-4. Uses of Polymer B
[0123] Polymer B can be used as a tackifier added to adhesive compositions. However, the uses of polymer B are not limited to the examples described above.
[0124] 2. Tougheners
[0125] 2-1. First Tackifier
[0126] The first tackifier in embodiments of the present invention comprises polymer B. The polymer B contained in the first tackifier includes, as described above, preferred examples. The first tackifier may contain one or more polymers B.
[0127] 2-2. Second Tackifier
[0128] The second tackifier according to embodiments of the present invention comprises a polymer C having a molecular weight of 1,500 to 30,000 Mw. Polymer C comprises a constituent unit derived from a monomer b having a double-bonded ring. Monomer b has two or more double-bonded rings in its side chain. The second tackifier may comprise one or more polymers C.
[0129] The range of Mw that polymer C can take is the same as the range of Mw that polymer B can take. Examples of constituent units derived from monomer b that polymer C can include are the same as examples of constituent units derived from monomer b having two or more double-bonded rings in the side chain that polymer B can include. For example, monomer b for polymer C can be a structure in which the first and second double-bonded rings in the side chain are bonded via linking groups. Additionally, monomer b for polymer C can be phenoxybenzyl acrylate.
[0130] The range of possible percentages of constituent units derived from monomer b in polymer C is the same as the range of possible percentages of constituent units derived from monomer b in polymer B.
[0131] Polymer C may also contain constituent units derived from monomers c other than monomer b. Examples of monomer c, and the ranges in which constituent units derived from each monomer c may be present in polymer C, are the same as those for examples of monomer c in polymer B, and the ranges in which constituent units derived from each monomer c may be present in polymer B.
[0132] 2-3. Uses of Tougheners
[0133] The first and second tackifiers can be added to the adhesive composition. The adhesive composition may be, for example, a light-curing type. The adhesive composition may be, for example, an acrylic adhesive composition. However, the uses of the first and second tackifiers are not limited to the examples described above. Furthermore, the types of adhesive compositions to which the first and second tackifiers can be added are not limited to the examples described above.
[0134] 3. Adhesive Compositions
[0135] The adhesive composition of this invention (hereinafter referred to as "adhesive composition A") comprises monomer component M, polymer B, and a first tackifier or a second tackifier. A portion of monomer component M may be formed as a partial polymer. Adhesive composition A is a photocurable adhesive composition that forms an adhesive sheet by irradiation with light. It should be noted that, compared to thermocurable adhesives that primarily utilize heat to form the adhesive sheet, photocurable adhesives can suppress the energy necessary for adhesive sheet formation; therefore, this is a particularly preferred method for environmental protection and sustainability purposes.
[0136] 3-1. Polymer B, First Tackifier, Second Tackifier
[0137] Regarding the polymer B, the first tackifier, and the second tackifier that may be included in adhesive composition A, they are as described above. Adhesive composition A may include one or more polymers B. Adhesive composition A may include one or more first tackifiers. Adhesive composition A may include one or more second tackifiers.
[0138] The content of polymer B in adhesive composition A, relative to 100 parts by weight of monomer component M, is, for example, 0.1 parts by weight or more, and can be 0.5 parts by weight or more, 1.0 parts by weight or more, 2.0 parts by weight or more, 3.0 parts by weight or more, 4.0 parts by weight or more, 5.0 parts by weight or more, 6.0 parts by weight or more, 7.0 parts by weight or more, 8.0 parts by weight or more, 9.0 parts by weight or more, 10.0 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, and further, 40 parts by weight or more. The upper limit of the above content is, for example, 60 parts by weight or less, and can be 55 parts by weight or less, 50 parts by weight or less, and further, 45 parts by weight or less.
[0139] When the adhesive composition A contains the inorganic particles described later, the content of polymer B, relative to 100 parts by weight of the monomer component M and the inorganic particles (specifically, a mixture of inorganic particles and dispersant), can be 0.1 parts by weight or more, or 0.5 parts by weight or more, 1 part by weight or more, 2 parts by weight or more, 3 parts by weight or more, 4 parts by weight or more, 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, 9 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, and further, 20 parts by weight or more. The upper limit of the content can be 50 parts by weight or less, or 40 parts by weight or less, 35 parts by weight or less, and further, 30 parts by weight or less. The content can also be 1 to 30 parts by weight, and further, 2 to 30 parts by weight.
[0140] The acceptable ranges for the content of the first tackifier and the second tackifier in adhesive composition A are the same as the acceptable ranges for the content of polymer B in adhesive composition A.
[0141] 3-2. Monomer Component M
[0142] <3-2-a. Monomers a containing double-bonded rings>
[0143] Monomer component M may contain monomer a, which has a double-bonded ring. Monomer a is a component suitable for increasing the refractive index of the adhesive sheet.
[0144] An instance of monomer a is the same as an instance of monomer b. Monomer a may be the same as monomer b or may be different.
[0145] In monomer a, the double-bonded ring is preferably an aromatic ring. Monomer a may contain two or more aromatic rings (preferably carbocyclic rings) in one molecule, and more preferably, it may contain monomers (containing multiple aromatic ring monomers) having two or more aromatic rings and at least one olefinic unsaturated group in one molecule. Monomer a may have a structure in which the first double-bonded ring and the second double-bonded ring contained in two or more double-bonded rings are bonded together via a linking group in the side chain. Particularly preferred monomer a contains phenoxybenzyl acrylate.
[0146] The content of monomer a in monomer component M is, for example, 30% by weight or more, and can be 50% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, more than 70% by weight, 75% by weight or more, 80% by weight or more, 85% by weight or more, 87% by weight or more, 90% by weight or more, 91% by weight or more, 92% by weight or more, 93% by weight or more, 94% by weight or more, 95% by weight or more, 96% by weight or more, 97% by weight or more, 98% by weight or more, and further can be 99% by weight or more. The upper limit of the above content is, for example, 100% by weight, which can be less than 98% by weight, less than 97% by weight, less than 96% by weight, less than 95% by weight, less than 93% by weight, less than 90% by weight, less than 90% by weight, less than 85% by weight, less than 80% by weight, less than 75% by weight, less than 70% by weight, less than 60% by weight, less than 50% by weight, less than 25% by weight, less than 10% by weight, and further can be less than 5% by weight.
[0147] When the adhesive composition A contains the inorganic particles described later, the content of monomer a may be 10 parts by weight or more, or 20 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 36 parts by weight or more, 37 parts by weight or more, 38 parts by weight or more, 39 parts by weight or more, 40 parts by weight or more, 41 parts by weight or more, 42 parts by weight or more, 43 parts by weight or more, 44 parts by weight or more, 45 parts by weight or more, 46 parts by weight or more, 47 parts by weight or more, 48 parts by weight or more, 49 parts by weight or more, 50 parts by weight or more, 51 parts by weight or more, 52 parts by weight or more, 53 parts by weight or more, 54 parts by weight or more, 55 parts by weight or more, 56 parts by weight or more, 57 parts by weight or more, 58 parts by weight or more, and further may be 59 parts by weight or more. The upper limit of the content can be below 90 parts by weight, or below 80 parts by weight, below 70 parts by weight, or even below 60 parts by weight. The content can also be 40 to 60 parts by weight.
[0148] <3-2-b. Other monomers>
[0149] Monomer component M may contain monomers d other than monomer a. Examples of monomer d are the same as examples of monomer c. Monomer component M may also not contain monomer d.
[0150] One example of monomer d is a hydroxyl-containing monomer. The content of the hydroxyl-containing monomer in monomer component M is, for example, 25% by weight or less, but can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, and further, 2% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain the hydroxyl-containing monomer.
[0151] Another example of monomer d is an alkyl (meth)acrylate having an alkyl group having 1 to 20 carbon atoms in its side chain. The content of the alkyl (meth)acrylate in monomer component M is, for example, 25% by weight or less, but can be 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, and further, 4% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain an alkyl (meth)acrylate.
[0152] Another example of monomer d is a monomer containing an aliphatic ring. The content of the aliphatic ring monomer in monomer component M is, for example, 25% by weight or less, but can be 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, and further, 4% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain the aliphatic ring monomer.
[0153] Another example of monomer d is a carboxyl-containing monomer. The content of the carboxyl-containing monomer in monomer component M is, for example, 10% by weight or less, and can be 7% by weight or less, 5% by weight or less, 3% by weight or less, or even 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, or even 1% by weight or more. Preferably, monomer component M does not contain carboxyl-containing monomers.
[0154] When the adhesive composition A contains the inorganic particles described later, the content of monomer d may be 30 parts by weight or less, or 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further may be 1.5 parts by weight or less. The lower limit of the content may be 0.01 parts by weight or more, or 0.1 parts by weight or more, 0.5 parts by weight or more, and further may be 1 part by weight or more.
[0155] When the adhesive composition A contains the inorganic particles described later, the content of monomer component M may be 10 parts by weight or more, or 20 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 36 parts by weight or more, 37 parts by weight or more, 38 parts by weight or more, 39 parts by weight or more, 40 parts by weight or more, 41 parts by weight or more, 42 parts by weight or more, 43 parts by weight or more, 44 parts by weight or more, 45 parts by weight or more, 46 parts by weight or more, 47 parts by weight or more, 48 parts by weight or more, 49 parts by weight or more, 50 parts by weight or more, 51 parts by weight or more, 52 parts by weight or more, 53 parts by weight or more, 54 parts by weight or more, 55 parts by weight or more, 56 parts by weight or more, 57 parts by weight or more, 58 parts by weight or more, 59 parts by weight or more, and further may be 60 parts by weight or more. The upper limit of the content can be below 90 parts by weight, or below 80 parts by weight, below 70 parts by weight, or even below 60 parts by weight. The content can also be 40 to 60 parts by weight.
[0156] 3-3. Some Polymers
[0157] Adhesive composition A may contain a portion of the polymer of monomer component M. This portion of the polymer can be any polymer from homopolymers and copolymers. The portion of the polymer moderately increases the viscosity of adhesive composition A, thereby contributing to the stable formation of the coating layer described later. It should be noted that adhesive composition A may also not contain the portion of the polymer.
[0158] The weight-average molecular weight of some polymers is greater than 30,000, but can be above 50,000, 100,000, 500,000, or even above 1 million. There is no specific upper limit to the weight-average molecular weight; for example, it can be below 3 million or below 2 million. The weight-average molecular weight is determined by GPC (gel permeation chromatography) and calculated using polystyrene conversion.
[0159] 3-4. Photopolymerization Initiators
[0160] Adhesive composition A typically contains a photopolymerization initiator. The photopolymerization initiator may be a photoradiogenerator that generates free radicals through visible light and / or ultraviolet light with wavelengths shorter than 450 nm.
[0161] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl acetophenones such as 1-hydroxycyclohexylphenyl ketone; substituted α-alcohol ketones such as 2-methyl-2-hydroxyphenylacetophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; and 1-phenyl... Photoactive oximes such as -1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone and other benzophenone compounds; thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone Thioxanone compounds such as isopropyl thioxanone, 2,4-diisopropyl thioxanone, and 2,4-diethyl thioxanone; 2,4,6-trichloro-triazine, 2-phenyl-4,6-bis(trichloromethyl)-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-triazine, and 2-piperyl-4,6-bis(trichloromethyl)-triazine. Triazine compounds, including 2,4-bis(trichloromethyl)-6-styryl-triazine, 2-(naphthyl-1-yl)-4,6-bis(trichloromethyl)-triazine, 2-(4-methoxy-naphthyl-1-yl)-4,6-bis(trichloromethyl)-triazine, 2,4-trichloromethyl-(piperyl)-6-triazine, and 2,4-trichloromethyl-(4'-methoxystyryl)-6-triazine; 1,2-octanedione, Oxime esters such as 1-[4-(phenylthio)-, 2-(O-benzoyl oxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethoxy)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide; quinone compounds such as 9,10-phenanthroquinone, camphorquinone, ethylanthraquinone; borate esters; carbazole compounds; imidazole compounds; and titanium ceramsite compounds. Adhesive composition A may contain one or more photopolymerization initiators.
[0162] Specific examples of photopolymerization initiators include 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad 651, manufactured by IGM Resins), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins), and 1-hydroxycyclohexylphenyl ketone (Omnirad 184, manufactured by IGM Resins).
[0163] The content of the photopolymerization initiator in the adhesive composition A is, for example, 0.02 to 10 parts by weight of monomer component M per 100 parts by weight, and can be 0.05 to 5 parts by weight, 0.1 to 3 parts by weight, or even 0.2 to 2 parts by weight.
[0164] When the adhesive composition A contains the inorganic particles described later, the content of the photopolymerization initiator may be 0.02 to 10 parts by weight, or 0.05 to 5 parts by weight, 0.1 to 3 parts by weight, or even 0.2 to 2 parts by weight, relative to a total of 100 parts by weight of monomer component M and inorganic particles (more specifically, a mixture of inorganic particles and dispersant).
[0165] 3-5. Inorganic Particles
[0166] Adhesive composition A may contain inorganic particles. Inorganic particles can help increase the refractive index of the adhesive sheet. Preferably, the inorganic particles are dispersed in adhesive composition A.
[0167] Inorganic particles can be selected from one or more metal compound particles and metal particles, for example, according to desired purposes such as increasing the refractive index. Metal compound particles can be metal oxide particles. Examples of materials constituting metal oxide particles are titanium oxide, zirconium oxide, cerium oxide, aluminum oxide, zinc oxide, tin oxide, copper oxide, barium titanate, and niobium oxide. Metal oxide particles can be used alone or in combination of two or more. The inorganic particles preferably include zirconium oxide, and can be zirconium oxide particles that are substantially composed of only zirconium oxide. Zirconia particles can help increase the refractive index of the adhesive sheet.
[0168] Materials constituting metal compound particles can be metal hydroxides such as aluminum hydroxide, boehmite, magnesium hydroxide, calcium hydroxide, zinc hydroxide, iron hydroxide, copper hydroxide, barium hydroxide, basic magnesium carbonate, and hydrotalcite, as well as hydrated metal compounds. Examples of materials constituting metal particles include iron, zinc, tungsten, and platinum.
[0169] Inorganic particle materials can be high-entropy alloys composed of a mixture of multiple elements.
[0170] The inorganic particles can be surface-treated materials. An example of surface treatment is hydrophobication. It should be noted that, in this specification, the inorganic particles preferably do not contain carbon black particles.
[0171] Inorganic particles can contain high-refractive-index materials. The refractive index of a high-refractive-index material is, for example, 1.60 or higher, and can be 1.70 or higher, 1.80 or higher, or even 2.00 or higher. There is no particular upper limit to the refractive index of high-refractive-index materials; for example, it can be below 3.00, and can be below 2.80, 2.50 or lower, or even below 2.20. The refractive index of the material contained in the inorganic particles can be determined by measuring the refractive index of a single-layer film of the corresponding material using a commercially available spectroellipsometer at 23°C and 549 nm. For example, a spectroellipsometer with the product name "EC-400" (manufactured by JA.Woolam) or its equivalent can be used.
[0172] Inorganic particles can be nanoparticles with an average particle size of less than 1 μm. The average particle size of inorganic particles can be less than 100 nm. The average particle size can be less than 70 nm, less than 50 nm, less than 30 nm, less than 20 nm, less than 15 nm, less than 10 nm, less than 7 nm, less than 5 nm, and further less than 4 nm. The lower limit of the average particle size is, for example, greater than 1 nm, greater than 1.5 nm, greater than 2 nm, and further greater than 2.5 nm. It should be noted that the average particle size can be determined as the median particle size (D50) in the particle size distribution measured by dynamic light scattering method.
[0173] Relative to the total of 100 parts by weight of monomeric component M and inorganic particles (specifically, a mixture of inorganic particles and dispersant), the content of inorganic particles may be, for example, 10 parts by weight or more, or 20 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 36 parts by weight or more, 37 parts by weight or more, 38 parts by weight or more, 39 parts by weight or more, 40 parts by weight or more, 41 parts by weight or more, 42 parts by weight or more, 43 parts by weight or more, 44 parts by weight or more, 45 parts by weight or more, 46 parts by weight or more, 47 parts by weight or more, 48 parts by weight or more, 49 parts by weight or more, 50 parts by weight or more, 51 parts by weight or more, 52 parts by weight or more, 53 parts by weight or more, 54 parts by weight or more, 55 parts by weight or more, 56 parts by weight or more, 57 parts by weight or more, 58 parts by weight or more, 59 parts by weight or more, and further may be 60 parts by weight or more. The upper limit of the above content is, for example, 90 parts by weight or less, but it can be 80 parts by weight or less, 70 parts by weight or less, or even 60 parts by weight or less. The above content is preferably 40 to 60 parts by weight.
[0174] 3-6. Dispersants
[0175] Adhesive composition A may contain a dispersant for inorganic particles. The dispersant is a component used to adequately disperse the inorganic particles in adhesive composition A. Preferably, the dispersant is in contact with the surface of the inorganic particles, and more preferably coats the surface of the inorganic particles.
[0176] An example of a dispersant is a compound having both a hydrophilic and a hydrophobic portion within a single molecule. It is presumed that the hydrophilic and hydrophobic portions of the dispersant exhibit relatively high affinity for both the inorganic particles and the monomeric component M. Dispersants may or may not possess polymerizable functional groups such as olefinic unsaturated groups.
[0177] The hydrophilic portion of the dispersant preferably has a hydrophilic group. Examples of hydrophilic groups include ether groups and ester groups.
[0178] The hydrophilic portion of the preferred dispersant has a functional group F that exhibits adsorption or reactivity with inorganic particles. Examples of functional group F are at least one selected from basic and acidic groups. Specific examples of functional group F are hydroxyl, carboxyl, nitrogen-containing, sulfur-containing, phosphorus-containing, and silicon-containing groups. The number of functional groups F in one molecule of the dispersant can be one or more (e.g., about 2 to 5). The two or more functional groups F present in one molecule can be of the same type or different types.
[0179] The hydrophilic portion of the dispersant can have a chain-like structure or a composite structure of chain-like and ring-like structures. For example, the dispersant may include: a structure in which a functional group F is linked to a hydrophobic portion via a chain-like structure; a structure in which the side chains of the chain-like structure connected to the hydrophobic portion at one end have the functional group F; and a structure in which the other end of the chain-like structure connected to the hydrophobic portion does not have the functional group F (e.g., the other end of the chain-like structure is a free end). The dispersant may have two or more of the above structures.
[0180] The dispersant can be an aliphatic compound. An aliphatic compound is represented, for example, by the following formula (1).
[0181] [Chemical Formula 1]
[0182] In formula (1), R is an alkyl group, preferably an alkyl group with 1 to 3 carbon atoms, more preferably an ethyl group. m is 1 to 10, preferably 2 to 8, more preferably 3 to 7. n is 5 to 20, preferably 8 to 12.
[0183] The dispersant can be an aromatic compound having an aromatic ring. Examples of aromatic rings are the same as those given in the descriptions of monomers a and b above.
[0184] The dispersant can be selected from known surfactants. Examples of surfactants include anionic surfactants (carboxylic acid type, phosphate ester type, sulfate ester type, sulfonic acid type, etc.), nonionic surfactants, cationic surfactants, and amphoteric surfactants. Anionic surfactants are preferred as dispersants.
[0185] The content of the dispersant relative to 100 parts by weight of inorganic particles is, for example, 0.1 parts by weight or more, 0.5 parts by weight or more, and further, 1.0 parts by weight or more. The upper limit of the above content is, for example, 30 parts by weight or less, and 20 parts by weight or less.
[0186] 3-7. Crosslinking Agent
[0187] Adhesive composition A may contain a crosslinking agent. Examples of crosslinking agents are polyfunctional monomers having two or more polymerizable functional groups in one molecule. The polyfunctional monomer may be a (meth)acrylic acid monomer. Examples of polyfunctional monomers include monomers having two or more C=C bonds in one molecule, and monomers having one or more C=C bonds and one or more epoxy, aziridinyl, or aziridine groups in one molecule. Monomers with polymerizable functional groups such as zolyl, hydrazine, and hydroxymethyl. Polyfunctional monomers are preferably monomers having two or more C=C bonds in one molecule.
[0188] Examples of multifunctional monomers include: polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and other multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.); allyl methacrylate, vinyl methacrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The multifunctional monomer is preferably a multifunctional acrylate, more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.
[0189] The content of the crosslinking agent in the adhesive composition A is, for example, 5 parts by weight or less per 100 parts by weight of monomer component M, and can be 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further, 0.5 parts by weight or less. The lower limit of the content is, for example, 0.01 parts by weight or more, and further, 0.05 parts by weight or more.
[0190] When the adhesive composition A contains inorganic particles, the content of the crosslinking agent is, for example, 5 parts by weight or less, and can be 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less, relative to a total of 100 parts by weight of monomer component M and inorganic particles (specifically, a mixture of inorganic particles and dispersant). The lower limit of the above content is, for example, 0.01 parts by weight or more, and can be 0.03 parts by weight or more, or even 0.05 parts by weight or more.
[0191] 3-8. Silane Coupling Agents
[0192] Adhesive composition A may contain a silane coupling agent. Specific examples of silane coupling agents include, for instance, epoxy-containing silane coupling agents such as 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)- 3-Aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-γ-aminopropyltrimethoxysilane and other aminosilane coupling agents; 3-acryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane and other (meth)acrylic acid silane coupling agents; 3-isocyanate propyltriethoxysilane and other isocyanate silane coupling agents, etc.
[0193] The content of the silane coupling agent in adhesive composition A is, for example, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further, 0.5 parts by weight or less, relative to 100 parts by weight of monomer component M. The lower limit of the content is, for example, 0.1 parts by weight or more, and further, 0.2 parts by weight or more. Adhesive composition A may also not contain a silane coupling agent.
[0194] When the adhesive composition A contains inorganic particles, the content of the silane coupling agent, relative to 100 parts by weight of the monomer component M and the inorganic particles (specifically, a mixture of inorganic particles and dispersant), is, for example, 5 parts by weight or less, and can be 3 parts by weight or less, 1 part by weight or less, 0.8 parts by weight or less, 0.5 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, 0.2 parts by weight or less, and further, 0.1 parts by weight or less. The lower limit of the above content is, for example, 0.01 parts by weight or more, and further, 0.05 parts by weight or more.
[0195] 3-9. Antioxidants
[0196] Adhesive composition A may contain an antioxidant. Examples of antioxidants include phenolic antioxidants, hindered phenolic antioxidants, amine antioxidants, and phosphite antioxidants.
[0197] Examples of phenolic antioxidants include monophenolic antioxidants, bisphenolic antioxidants, and high molecular weight phenolic antioxidants. Examples of monophenolic antioxidants include 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, and stearate β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. Examples of bisphenol antioxidants include 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), and 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane. Examples of high molecular weight phenolic antioxidants include 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetra[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis(4'-hydroxy-3'-tert-butylphenyl)butyrate]ethylene glycol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocopherol.
[0198] Hindered phenolic antioxidants can have a structure in which at least one carbon atom adjacent to the carbon atom on the aromatic ring bonded to the OH group of the phenol is bonded with a tert-butyl group. Examples of hindered phenolic antioxidants include butylated hydroxytoluene (BHT); and Irganox 1010, Irganox 1010FF, Irganox 1035, Irganox 1035FF, Irganox 1076, Irganox 1076FD, Irganox 1076DWJ, Irganox 1098, Irganox 1135, Irganox 1330, Irganox 1726, Irganox 1425WL, Irganox 1520L, Irganox 245, Irganox 245FF, Irganox 259, Irganox 3114, Irganox 565 and Irganox 295 (all trade names, manufactured by BASF).
[0199] Amine antioxidants are preferably hindered amine antioxidants. Hindered amine antioxidants may have at least one hindered piperazine group in one molecule. Examples of hindered amine antioxidants are ADEKA STAB LA-63, ADEKA STAB LA-63P, ADEKA STAB LA-52, and ADEKA STAB LA-57 (all trade names, manufactured by ADEKA).
[0200] Examples of phosphite antioxidants include triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite; as well as ADEKA STAB 2112, ADEKA STAB 2112RG, ADEKA STAB 1178, and ADEKA STAB 3010 (all trade names, manufactured by ADEKA).
[0201] The antioxidant content in adhesive composition A is, for example, 5 parts by weight or less per 100 parts by weight of monomer component M, and can be 3 parts by weight or less, 1 part by weight or less, 0.8 parts by weight or less, or even 0.5 parts by weight or less. The lower limit of the above content is, for example, 0.01 parts by weight or more, and even more than 0.05 parts by weight. Adhesive composition A may also not contain antioxidant.
[0202] When the adhesive composition A contains inorganic particles, the antioxidant content is, for example, 5 parts by weight or less, or 3 parts by weight or less, 1 part by weight or less, 0.8 parts by weight or less, or even 0.5 parts by weight or less, relative to a total of 100 parts by weight of monomer component M and inorganic particles (specifically, a mixture of inorganic particles and dispersant). The lower limit of the above content is, for example, 0.01 parts by weight or more, or even 0.05 parts by weight or more.
[0203] 3-10. Ultraviolet Absorbers
[0204] Adhesive composition A may contain a UV absorber (UVA). Examples of UVA include triazine UVA, benzotriazole UVA, benzophenone UVA, hydroxybenzophenone UVA, salicylate UVA, and cyanoacrylate UVA. Each UVA is a compound having a triazine backbone, a benzotriazole backbone, a benzophenone backbone, a hydroxybenzophenone backbone, a salicylate structure, or a cyanoacrylate structure. The UVA is preferably a triazine or benzotriazole UVA, more preferably a benzotriazole UVA.
[0205] Examples of triazine UVA derivatives include 2,4-bis[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN460, manufactured by BASF), the reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl with [(C10-C16 (mainly C12-C13)alkoxy)methyl]ethylene oxide (TINUVIN400, manufactured by BASF), and 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-[ 3-(dodecyloxy)-2-hydroxypropoxy]phenol, 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine reacting with (2-ethylhexyl) epoxypropionate (TINUVIN 405, BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]phenol (TINUVIN 1577, BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol (ADK STAB LA46, ADEKA), 2-(2-hydroxy-4-[1-octoxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN 479, BASF).
[0206] Examples of benzotriazole UVA derivatives include 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2H-1,2,3-benzotriazole-2-yl)-6-dodecyl-4-methylphenol (TINUVIN 571, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVINPS, manufactured by BASF), phenylpropionic acid, and 3-(2H-benzotriazole-2-yl)-5-(1, Ester compounds of 1-dimethylethyl)-4-hydroxy (C7-9 side chain and straight-chain alkyl) (TINUVIN 384-2, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 900, manufactured by BASF), the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 (TINUVIN 1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN) P, manufactured by BASF), 2(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (TINUVIN328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol ( TINUVIN 329 (manufactured by BASF), the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (TINUVIN 213 (manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN 571 (manufactured by BASF), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole (Sumisorb 250 (manufactured by Sumitomo Chemical Industry)).
[0207] The UVA content in adhesive composition A is, for example, 10 parts by weight or less, 5 parts by weight or less, 3 parts by weight or less, and further, 2 parts by weight or less, relative to 100 parts by weight of monomer component M. The lower limit of the above content is, for example, 0.1 parts by weight or more, 0.5 parts by weight or more, and further, 1 part by weight or more. Adhesive composition A may also not contain UVA.
[0208] When the adhesive composition A contains inorganic particles, the UVA content is, for example, 10 parts by weight or less, 5 parts by weight or less, 3 parts by weight or less, and further, 2 parts by weight or less, relative to 100 parts by weight of the total monomer component M and inorganic particles (specifically, a mixture of inorganic particles and dispersant). The lower limit of the above content is, for example, 0.1 parts by weight or more, 0.5 parts by weight or more, and further, 1 part by weight or more.
[0209] 3-11. Solvents
[0210] The solvent content in adhesive composition A is, for example, 5% by weight or less, and can be 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further, 0.5% by weight or less. Adhesive composition A may substantially not contain solvent. Substantially not containing solvent means that it is permissible to include solvents from additives or the like at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, more preferably 0.01% by weight or less.
[0211] 3-12. Additives
[0212] Adhesive composition A may also contain additives other than those mentioned above. Examples of additives include chain transfer agents, viscosity modifiers, tackifiers, plasticizers, softeners, anti-aging agents, fillers, colorants, surfactants, and antistatic agents.
[0213] "3-13. Physical Properties"
[0214] The viscosity of the preferred adhesive composition A is 5 to 150 poise at 25°C. Adhesive composition A with a viscosity within the above range is particularly suitable for the formation of the coating layer described later.
[0215] 3-14. Manufacturing Method
[0216] Adhesive composition A can be prepared by mixing its components. Adhesive composition A containing inorganic particles can be prepared by the following method: First, a dispersion is prepared by dispersing the inorganic particles in a solvent. This dispersion is then mixed with a dispersant and at least a portion of the monomers contained in monomer component M. The solvent is removed from the resulting mixture, thereby preparing a dispersion containing inorganic particles, a dispersant, and monomers. The method for removing the solvent from the mixture is not particularly limited; methods such as vacuum removal can be used. Next, the remaining monomers, polymer B, and a photopolymerization initiator are added to the dispersion and mixed. Thus, adhesive composition A containing inorganic particles can be prepared.
[0217] 4. Adhesive Sheet
[0218] 4-1. Adhesive Sheet
[0219] An example of an adhesive sheet according to an embodiment of the present invention is shown below. Figure 1 . Figure 1 Adhesive sheet 1 is an adhesive sheet formed from adhesive composition A. Adhesive sheet 1 contains polymer B derived from adhesive composition A.
[0220] The polymerization rate of monomer component M in adhesive sheet 1 is preferably 90% or higher. The polymerization rate can be 95% or higher, 98% or higher, or even 99% or higher.
[0221] The gel fraction of the adhesive sheet 1 is, for example, 50% or more, and can be 75% or more, 80% or more, 85% or more, and even 90% or more.
[0222] The refractive index of the adhesive sheet 1 is, for example, 1.55 or higher, and can be 1.56 or higher, 1.57 or higher, 1.58 or higher, 1.59 or higher, 1.60 or higher, 1.61 or higher, 1.62 or higher, 1.63 or higher, 1.64 or higher, 1.645 or higher, and further can be 1.65 or higher. The upper limit of the refractive index is, for example, 1.80 or lower, and can be 1.79 or lower, 1.78 or lower, 1.77 or lower, 1.76 or lower, 1.75 or lower, 1.74 or lower, 1.73 or lower, 1.72 or lower, 1.71 or lower, 1.70 or lower, 1.69 or lower, 1.68 or lower, 1.67 or lower, and further can be 1.66 or lower. The upper limit of the refractive index can be 1.65 or lower, 1.64 or lower, and further can be 1.63 or lower, depending on the situation. A preferred example of the refractive index of the adhesive sheet 1 is 1.63 to 1.66. Another preferred example of the refractive index of the adhesive sheet 1 is 1.60 to 1.63. Optical substrates that can be included in the optical laminate include those with high refractive indexes. Using the adhesive sheet 1 with a high refractive index in the bonding of high refractive index optical substrates is beneficial for reducing reflected light at the interface between the optical substrate and the adhesive sheet.
[0223] In this specification, the refractive index of adhesive sheet 1 refers to the refractive index of the surface of adhesive sheet 1. The refractive index of adhesive sheet 1 can be measured using a prism coupler at a measurement temperature of 25°C and a measurement wavelength of 594 nm. For adhesive sheets 1 with a thickness less than 20 μm, measurements based on the light propagation mode are generally suitable. For adhesive sheets 1 with a thickness of 20 μm or more, measurements based on the critical angle mode are generally suitable. A commercially available measuring device can be used, for example, the Metricon 2010 / M prism coupler or its equivalent.
[0224] The haze of the adhesive sheet 1 can be, for example, 5.0% or less, less than 3.0%, 2.5% or less, 2.0% or less, 1.7% or less, 1.5% or less, 1.2% or less, 1.0% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, 0.5% or less, 0.4% or less, 0.3% or less, and further, 0.2% or less. The lower limit of haze is not particularly limited and can be 0.1% or more. The low-haze adhesive sheet 1 is particularly suitable for applications involving optical laminates.
[0225] In this specification, haze refers to the ratio of diffused transmitted light to total transmitted light when visible light is irradiated onto the adhesive sheet 1, which is the object of measurement. Haze can be calculated using the following formula. In the formula, Th is the haze (%), Td is the diffuse light transmittance, and Tt is the total light transmittance.
[0226] Th(%)=Td / Tt×100
[0227] The chromaticity of adhesive sheet 1 conforms to CIE 1976 L as specified in JIS Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value can be below 2.0. (Chromaticity) The absolute value can be below 1.7, below 1.5, below 1.2, below 1.0, below 0.9, below 0.8, below 0.7, below 0.6, and even below 0.5. (Color intensity) The lower limit of the absolute value is, for example, above 0, and can be above 0.1. The chromaticity of adhesive sheet 1. The evaluation can be performed using a commercially available colorimeter capable of performing measurements based on JIS Z8781-4:2013.
[0228] The content of acidic groups (especially COOH groups) in polymer B contained in adhesive sheet 1 is, for example, 0.1% by weight or less, less than 0.01% by weight, and even less than 0.001% by weight. Preferably, polymer B does not contain acidic groups. The content of acidic groups can be determined, for example, by the following method. First, the sol component (uncrosslinked component) contained in adhesive sheet 1 is extracted using a solvent (e.g., toluene). The component (polymer B) with a weight average molecular weight of 1500 to 30000 is separated and extracted using preparative GPC (gel permeation chromatography). The component is dried in an oven at 130°C for 2 hours to remove the solvent. The dried and solidified component is evaluated by infrared spectroscopy, thereby determining the content of acidic groups.
[0229] The bonding strength between the adhesive sheet 1 and the alkali-free glass is preferably 0.5N / 25mm or more, but can also be 0.7N / 25mm or more, 0.8N / 25mm or more, 1.0N / 25mm or more, 1.2N / 25mm or more, 1.5N / 25mm or more, 1.7N / 25mm or more, 2.0N / 25mm or more, 2.2N / 25mm or more, 2.5N / 25mm or more, 2.7N / 25mm or more, 3.0N / 25mm or more, 3.5N / 25mm or more, 4.0N / 25mm or more, 4.5N / 25mm or more, 5.0N / 25mm or more, 6.0N / 25mm or more, 7.0N / 25mm or more, 8.0N / 25mm or more, 9.0N / 25mm or more, and further can be 10.0N / 25mm or more. The upper limit of the aforementioned adhesive force is, for example, 50.0 N / 25 mm or less, but can be 40.0 N / 25 mm or less, 30.0 N / 25 mm or less, 25.0 N / 25 mm or less, and further, 20.0 N / 25 mm or less. Depending on the circumstances, the upper limit of the aforementioned adhesive force can be 10.0 N / 25 mm or less, 5.0 N / 25 mm or less, and further, 4.0 N / 25 mm or less. A preferred example of the aforementioned adhesive force is 1.0 to 4.0 N / 25 mm. Another preferred example of the aforementioned adhesive force is 3.0 to 25.0 N / 25 mm.
[0230] The aforementioned adhesive strength can be determined by the following method. First, in a testing environment of 23°C and 50%RH, a laminate comprising an adhesive sheet 1 and a substrate is prepared. The substrate is not particularly limited as long as it supports the adhesive sheet 1 and does not affect the test results of the adhesive strength. For example, the substrate can be a film made of polyethylene terephthalate. Next, a strip of 100mm x 25mm is cut from the laminate to serve as a test piece. Then, the test piece is laminated onto alkali-free glass via the adhesive sheet 1, and a 2kg roller is used to press them together once. Alkali-free glass is glass that substantially does not contain alkali components (alkali metal oxides); specifically, the weight percentage of alkali components in the glass is, for example, 1000ppm or less, and further, 500ppm or less. Alkali-free glass is, for example, in sheet form and has a thickness of 0.5mm or more.
[0231] After being placed in the aforementioned environment for 30 minutes, the test piece was placed in a pressure degassing apparatus (autoclave) and subjected to autoclaving treatment at 50°C and 0.5 MPa for 30 minutes. Next, it was placed in an atmosphere of 23°C and 50% RH for 24 hours. Then, using a universal tensile and compression testing machine, the test piece was peeled from the alkali-free glass at a peel speed of 300 mm / min and a peel angle of 180°. The force necessary to peel the test piece from the alkali-free glass (peel strength) was then determined as the adhesive force.
[0232] The thickness of the adhesive sheet 1 is, for example, 500 μm or less, but can be 250 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, and further, 20 μm or less. The lower limit of the thickness of the adhesive sheet 1 is, for example, 2 μm or more, and can be 5 μm or more. The lower limit of the thickness of the adhesive sheet 1 can be 20 μm or more, or 30 μm or more, depending on the circumstances. A preferred example of the thickness of the adhesive sheet 1 is 2 to 30 μm. Another preferred example of the thickness of the adhesive sheet 1 is 30 to 100 μm.
[0233] 4-2. Manufacturing Method
[0234] The adhesive sheet 1 formed from the adhesive composition A can be formed, for example, by irradiating a first laminate 10 comprising a substrate sheet 11, a coating layer 12 containing the adhesive composition A, and a release liner 13 with light 14 (see reference). Figure 2 The coating layer 12 is cured by irradiation with light 14, forming the adhesive sheet 1. Typically, the irradiation with light 14 is performed from one side of the substrate sheet 11. In this case, the light 14 passes through the substrate sheet 11 and reaches the coating layer 12, causing the coating layer 12 to cure. However, it should be noted that the irradiation with light 14 can also be performed from one side of the release liner 13, or from both sides of the release liner 13 and the substrate sheet 11.
[0235] The formed adhesive sheet 1 is sandwiched between the substrate sheet 11 and the release liner 13 until the release liner 13 is peeled off, thus forming part of the second laminate 17. By peeling the release liner 13 from the second laminate 17, a third laminate 15 comprising the substrate sheet 11 and the adhesive sheet 1 is obtained. In the third laminate 15, the surface of the adhesive sheet 1 is exposed. Optical films can be laminated directly or via other layers relative to the exposed surface of the adhesive sheet 1.
[0236] Light 14 is, for example, visible light or ultraviolet light with a wavelength shorter than 450 nm. The light may contain wavelengths in the same region as the absorption wavelength of the photopolymerization initiator contained in the adhesive composition A. Light obtained by blocking short-wavelength light below 300 nm through a filter or the like can be irradiated; blocking the short-wavelength light is suitable for suppressing the deterioration of the substrate sheet 11 and / or release liner 13 caused by light 14. The light source 18 of light 14 is, for example, a lighting device equipped with an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps include ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black lights, chemical lamps, germicidal lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.
[0237] The illuminance of light 14 irradiating the first layer stack 10 (specifically, the coating layer 12) is, for example, 2.0~30 mW / cm². 2 The illuminance can be 2.5 mW / cm². 2 Above, 3.0mW / cm 2 Above, 3.5mW / cm 2 Above, 4.0mW / cm 2 Above, 5.0mW / cm 2 Above, 6.0mW / cm 2 Above, 7.0mW / cm 2 Above, 8.0mW / cm 2 Above, 9.0mW / cm 2 The above, and thus can be 10mW / cm 2 The above. The upper limit for illuminance is, for example, 25 mW / cm². 2 The following can be 20mW / cm 2 the following.
[0238] The duration of illumination 14 on the first layer stack 10 (specifically, the coating layer 12) is, for example, from 10 seconds to 1000 seconds, and can be 60 seconds or more, 100 seconds or more, 150 seconds or more, and further, 200 seconds or more. The upper limit of the duration is, for example, 800 seconds or less, and can be 600 seconds or less, 500 seconds or less, 400 seconds or less, 300 seconds or less, and further, 250 seconds or less. The illumination 14 can be continuous or intermittent.
[0239] The cumulative light intensity of light 14 for the first layer stack 10 (specifically, coating layer 12) is, for example, 25 mJ / cm. 2 The above can be 100mJ / cm 2 Above 500mJ / cm 2 Above, 1000mJ / cm 2 Above, 2000mJ / cm 2 Above, 2500mJ / cm 2 Above, 3000mJ / cm 2 Above 5000mJ / cm 2 Above, 7500mJ / cm 2 The above, and thus can be 10000mJ / cm 2 That's all. There is no specific upper limit for the cumulative light intensity, for example, 30000 mJ / cm². 2 The following can be 25000mJ / cm 2 Below, 20000mJ / cm 2 The following, and thus can be 18000mJ / cm 2 the following.
[0240] Light 14 can irradiate the first layer stack 10 in multiple stages. The illuminance and / or cumulative light intensity of light 14 in each stage can be the same or different. In addition, the light sources in each stage can be the same or different.
[0241] An example of the substrate for peeling liner 13 (hereinafter referred to as "liner substrate") is a resin film. Examples of resins that may be included in the liner substrate include polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth)acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0242] The release liner 13 may also have layers other than the substrate. The release liner 13 may have a release layer. For example, the release liner 13 may have a substrate and a release layer formed on one side of the substrate. The release liner 13 can be used such that the release layer is on the side of the coating layer 12. Typically, the release layer is a cured layer of a release agent composition containing a release agent. Various release agents can be used, such as silicone-based release agents, fluorinated release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder.
[0243] The peeling liner 13 can be in the form of a single sheet or in the form of a strip.
[0244] An example of substrate sheet 11 is a resin film. Examples of resins contained in substrate sheet 11 are the same as examples of resins that may be contained in a liner substrate.
[0245] The thickness of the substrate sheet 11 is, for example, 10~200μm, or 25~150μm.
[0246] The substrate sheet 11 may have a release layer on one side of the coating layer 12. Examples of release layers that the substrate sheet 11 may have are the same as examples of release layers that the release liner 13 may have. Alternatively, release layers may be present on both the release liner 13 and the substrate sheet 11.
[0247] The substrate sheet 11 can typically be selected as a sheet with a greater peel force to the adhesive sheet 1 compared to the release liner 13.
[0248] The substrate sheet 11 can be a single sheet or a strip.
[0249] The first laminate 10 can be formed, for example, by forming a coating layer 12 on a substrate sheet 11 (or release liner 13) and placing a release liner 13 (or substrate sheet 11) on the formed coating layer 12. Alternatively, the first laminate 10 can be formed by coating in such a way that a photocurable composition flows into a space between a substrate sheet 11 and a release liner 13 held at a given interval with their main surfaces facing each other.
[0250] The coating layer 12 can be formed by various coating methods such as roller coating, roller licking coating, gravure coating, reverse coating, roller brushing, spraying, dip roller coating, bar coating, scraping coating, air knife coating, curtain coating, die lip coating, and die coating.
[0251] The thickness of the coating layer 12 can be adjusted according to the thickness of the target adhesive sheet 1, for example, it can be less than 500 μm, less than 250 μm, less than 150 μm, less than 100 μm, less than 50 μm, less than 30 μm, less than 25 μm, and even less than 20 μm. The lower limit of the thickness of the coating layer 12 is, for example, more than 2 μm, and can be more than 5 μm.
[0252] The first laminate 10 may include a strip-shaped substrate sheet 11, a strip-shaped coating layer 12, and a strip-shaped release liner 13; in other words, it may be strip-shaped. The strip-shaped first laminate 10 can be obtained, for example, by forming the coating layer 12 between the substrate sheet 11 and the release liner 13 while they are being continuously fed from the winding body.
[0253] 5. Optical Laminates
[0254] An example of an optical laminate according to an embodiment of the present invention is shown below. Figure 3 . Figure 3 The optical laminate 20A includes an adhesive sheet 1 and an optical film 2. The adhesive sheet 1 and the optical film 2 are laminated together. The optical laminate 20A can be used in the form of an optical film with an adhesive sheet.
[0255] Examples of optical film 2 are polarizing films, retardation films, and laminated films comprising polarizing films and / or retardation films. However, optical film 2 is not limited to the examples described above. Optical film 2 may also comprise a glass film.
[0256] Optical film 2 is a polarizing film, and adhesive sheet 1 can be attached to optical film 2.
[0257] A polarizing film includes a polarizer. Typically, a polarizing film includes a polarizer and a protective film (a transparent protective film). The protective film is disposed in contact with the ground, for example, the main surface (the surface with the widest area) of the polarizer. The polarizer may be disposed between two protective films. The protective film may be disposed on at least one side of the polarizer.
[0258] There are no particular limitations on what constitutes a polarizer. Examples include: polarizers obtained by uniaxially stretching hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, after adsorbing dichroic substances such as iodine and dichroic dyes onto them; and polyene-oriented films such as dehydrated polyvinyl alcohol products and dehydrochlorinated polyvinyl chloride products. Typically, a polarizer is formed from a polyvinyl alcohol film (which may contain partially saponified ethylene-vinyl acetate copolymer films) and dichroic substances such as iodine.
[0259] The thickness of the polarizer is not particularly limited; for example, it can be less than 80 μm, less than 50 μm, less than 30 μm, less than 25 μm, and even less than 20 μm. The lower limit of the polarizer's thickness is not particularly limited; for example, it can be greater than 1 μm, greater than 5 μm, greater than 10 μm, and even greater than 15 μm. The dimensional variation of thin polarizers (e.g., less than 20 μm thick) is suppressed, which contributes to the improved durability of the optical laminate, especially its durability at high temperatures.
[0260] As materials for the protective film, thermoplastic resins with excellent properties such as transparency, mechanical strength, thermal stability, moisture barrier properties, and isotropy can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The protective film material can be thermosetting resins or UV-curable resins such as (meth)acrylic acid, urethane, acrylate urethane, epoxy, and silicone. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different. For example, a protective film formed of thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of thermosetting resin or UV-curable resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of additives include: ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0261] The thickness of the protective film can be appropriately determined. Generally speaking, it is about 10~200μm, considering factors such as strength, processability, operability, and thinness.
[0262] Polarizing lenses and protective films are typically bonded together using water-based adhesives. Examples of water-based adhesives include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latexes, waterborne polyurethane, and waterborne polyester. Other adhesives besides those mentioned above include UV-curable adhesives and electron beam-curable adhesives. Electron beam-curable polarizing film adhesives exhibit suitable adhesion to various protective films. The adhesive may also contain metallic compound fillers.
[0263] In polarizing films, a phase retardation film or similar material can be formed on the polarizer to replace the protective film. Alternatively, another protective film or a phase retardation film can be applied to the protective film.
[0264] Regarding the protective film, a hard coating can also be applied to the surface opposite to the surface to which the polarizer is bonded, and it can also be treated for purposes such as anti-reflection, anti-adhesion, diffusion, and anti-glare.
[0265] The polarizing film can be a circularly polarizing film.
[0266] The thickness of the polarizing film is, for example, less than 500 μm, less than 300 μm, less than 200 μm, less than 100 μm, and further less than 60 μm. The lower limit of the thickness is, for example, more than 10 μm, more than 25 μm, and further more than 40 μm.
[0267] A retardation film is a film that exhibits birefringence in the in-plane direction and / or the thickness direction. Examples of retardation films include stretched resin films and films obtained by aligning and immobilizing liquid crystal materials.
[0268] The retardation film can be a λ / 4 waveplate, a λ / 2 waveplate, a retardation film for antireflection (see, for example, paragraphs 0221, 0222, and 0228 of Japanese Patent Application Publication No. 2012-133303), a retardation film for viewing angle compensation (see, for example, paragraphs 0225 and 0226 of Japanese Patent Application Publication No. 2012-133303), or a tilted-orientation retardation film for viewing angle compensation (see, for example, paragraph 0227 of Japanese Patent Application Publication No. 2012-13303). The retardation film is not limited to the examples mentioned above as long as it has birefringence in the in-plane direction and / or the thickness direction. There are no limitations on the phase difference value, arrangement angle, three-dimensional birefringence, or whether it is a single layer or multiple layers. Known films can be used for the retardation film.
[0269] The thickness of the optical film 2 is, for example, 1~200 μm.
[0270] The optical film 2 can be a single layer or a laminated film consisting of two or more layers. When the optical film 2 is a laminated film, the bonding of the layers can be achieved using an adhesive sheet 1.
[0271] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 4 . Figure 4 The optical laminate 20B has a laminated structure in which a release liner 3, an adhesive sheet 1, and an optical film 2 are sequentially stacked. The optical laminate 20B can be used as an optical film with an adhesive sheet by peeling off the release liner 3.
[0272] The release liner 3 is typically a resin film. Examples of resins constituting the release liner 3 include polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene and polypropylene, polycarbonate, acrylics, polystyrene, polyamide, and polyimide. The side of the release liner 3 that is in contact with the adhesive sheet 1 may also be subjected to a release treatment. The release treatment may be, for example, a treatment using an organosilicon compound. However, the release liner 3 is not limited to the examples described above. The release liner 3 can be released when using the optical laminate 20B, for example, when it is adhered to the image forming layer.
[0273] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 5 . Figure 5 The optical laminate 20C has a laminated structure in which a release liner 3, an adhesive sheet 4, a retardation film 2B, an adhesive sheet 1, and a polarizing film 2A are sequentially stacked. The optical laminate 20C can be used by peeling off the release liner 3 and then attaching it to, for example, an image forming layer.
[0274] Adhesive sheet 4 can be a known adhesive sheet. Adhesive sheet 1 can be used for adhesive sheet 4.
[0275] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 6 . Figure 6 The optical laminate 20D has a stacked structure in which a release liner 3, an adhesive sheet 4, a retardation film 2B, an adhesive sheet 1, a polarizing film 2A, and a protective film 5 are sequentially stacked. The optical laminate 20D can be used by peeling off the release liner 3 and then attaching it to, for example, an image forming layer.
[0276] The protective film 5 protects the outermost optical film 2 (polarizer 2A) during the handling and storage of the optical laminate 20D, and also when the optical laminate 20D is introduced into the image display device. Furthermore, when introduced into the image display device, the protective film 5 can function as a window to the external space. The protective film 5 is typically a resin film. The resin constituting the protective film 5 is, for example, polyester such as PET, polyolefins such as polyethylene and polypropylene, acrylics, cycloolefins, polyimide, and polyamide, preferably polyester. However, the protective film 5 is not limited to the above examples. The protective film 5 can be a glass film or a laminate containing a glass film. Surface treatments such as anti-glare, anti-reflection, and antistatic treatments can be applied to the protective film 5.
[0277] The protective film 5 can be bonded to the optical film 2 using any adhesive. It can also be bonded using the adhesive sheet 1.
[0278] An optical laminate can have any configuration as long as it has an adhesive sheet 1 and an optical film 2.
[0279] The adhesive sheet 1 can be disposed between any layers of the optical laminate. In other words, the adhesive sheet 1 can be a so-called interlayer adhesive layer.
[0280] The optical laminates of the embodiments of the present invention can be distributed and stored, for example, in the form of a wound body formed by winding a strip of optical laminates, or in the form of a single sheet of optical laminates.
[0281] Typically, the optical laminates of embodiments of the present invention can be used in image display devices. Image display devices are, for example, EL displays such as liquid crystal displays, organic EL displays, and inorganic EL displays.
[0282] 6. Image Display Devices
[0283] An example of an image display device according to an embodiment of the present invention is shown below. Figure 7 . Figure 7 The image display device 21 has a stacked structure in which a substrate 7, an image forming layer (e.g., an organic EL layer or a liquid crystal layer) 6, an adhesive sheet 4, a phase retardation film 2B, an adhesive sheet 1, a polarizing film 2A, and a protective film 5 are sequentially stacked. Figure 6 The optical laminate 20D (excluding the release liner 3). The image display device 21 may also have Figures 3-5 Optical laminates 20A, 20B, and 20C are used instead of optical laminate 20D. The substrate 7 and the image forming layer 6 may have the same configuration as those of the substrate and image forming layer in a known image display device.
[0284] Figure 7 The image display device 21 can be an organic EL display or a liquid crystal display. However, the image display device 21 is not limited to this example. The image display device 21 can also be an electroluminescent (EL) display, a plasma display (PD), a field emission display (FED), etc. The image display device 21 can be used for home appliances, automotive applications, public information displays (PIDs), etc.
[0285] The image display device 21 can have any configuration as long as it has the adhesive sheet 1 and / or the optical laminate 20.
[0286] Example
[0287] The present invention will be specifically described below through embodiments, but the present invention is not limited to these embodiments in any way.
[0288] <Synthesis of Polymer B1>
[0289] In a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser, 99 parts by weight of POB-A, 1 part by weight of 4-hydroxybutyl acrylate (4HBA), 0.30 parts by weight of 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) as a polymerization initiator, 3 parts by weight of 1-thioglycerol as a chain transfer agent, and 300 parts by weight of ethyl acetate were added. The mixture was kept at 70°C and nitrogen was introduced slowly while stirring to allow for nitrogen purging for at least 1 hour. The liquid temperature in the flask was then maintained at 72-74°C for 6 hours to prepare a polymer B1 solution. Next, the solution was heated at 90°C for 12 hours, followed by vacuum treatment at 120°C for 3 hours to remove the ethyl acetate. Thus, a thoroughly dried polymer B1 was obtained, with less than 0.1 parts by weight of ethyl acetate as detected by gas chromatography.
[0290] <Synthesis of Polymers B2~B16>
[0291] The types and contents of monomers, polymerization initiators and chain transfer agents were changed as described in Table 1. Otherwise, polymers B2 to B16, which were thoroughly dried, were synthesized using the same method as polymer B1.
[0292] [Mw of polymer B]
[0293] The Mw of the obtained polymer B was determined by GPC (gel permeation chromatography). The measuring apparatus and conditions were set as described below. It should be noted that the measuring apparatus and conditions differ for nitrogen-containing and nitrogen-free compositions.
[0294] (Nitrogen-containing composition)
[0295] • Analytical apparatus: Agilent, 1200
[0296] • Chromatographic column: Tosoh, TSKgel SuperAWM-H + superAW4000 + superAW2500
[0297] Column temperature: 40℃
[0298] • Elution buffer: DMF (with added salt)
[0299] • Flow rate: 0.4 mL / min
[0300] Injection volume: 40μL
[0301] • Detector: Differential refractive index detector (RI)
[0302] • Standard sample: Agilent, polystyrene (PS)
[0303] (Nitrogen-free composition)
[0304] • Analytical apparatus: Waters, Alliance
[0305] • Chromatographic column: Tosoh, TSKgel SuperHZM-H × 2 columns
[0306] Column temperature: 40℃
[0307] • Elution buffer: THF
[0308] • Flow rate: 0.2 mL / min
[0309] Injection volume: 30μL
[0310] • Detector: Differential refractive index detector (RI)
[0311] • Standard sample: Agilent, polystyrene (PS)
[0312] The abbreviations in Table 1 are as follows.
[0313] POB-A: Phenoxybenzyl acrylate (manufactured by Kyoei Chemicals, trade name "LIGHT ACRYLATE POB-A")
[0314] 4HBA: 4-Hydroxybutyl acrylate
[0315] ACMO: Acryloylmorpholine
[0316] BA: n-Butyl acrylate
[0317] CHMA: Cyclohexyl methacrylate
[0318] IBXMA: Isoborneol Methacrylate
[0319] CBA: 2-(2-ethoxyethoxy)ethyl acrylate
[0320] NVP: N-vinylpyrrolidone
[0321] St: Styrene
[0322] AIBN: Azo polymerization initiator, 2,2'-azobisisobutyronitrile (manufactured by Kishida Chemical Co., Ltd.)
[0323] [Tg of polymer B]
[0324] The Tg of polymer B was determined using DSC and the method described above. A TAINSTRUMENTS Q2000 differential scanning calorimeter was used. The sample amount of polymer B for DSC determination was set to approximately 5 mg.
[0325] [Refractive index of polymer B]
[0326] Using the above method, the refractive index of polymer B was measured using an Abbe refractometer (ATAGO, model DR-M4) at a measurement wavelength of 589 nm and a measurement temperature of 25 °C.
[0327] [HSP of polymer B]
[0328] Using HSP (version 5), the HSP (δD, δP, δH) of polymer B was determined by calculation based on the constituent units of polymer B and the content of those units in polymer B.
[0329] [Color of Polymer B] [absolute value]
[0330] The color of polymer B was determined using the method described above. absolute value (| The measurements were performed. The analytical apparatus used was a Hitachi High-Tech UH4150 UV-Vis-NIR spectrophotometer. The analysis software used was Hitachi High-Tech UV Solutions.
[0331] The evaluation results for each property of polymers B1 to B16 are shown in Table 2 below.
[0332]
[0333] <Preparation of Dispersion D1>
[0334] Synthesis of dispersant d1
[0335] Relative to 1.0 mol of propionic acid, 8.0 mol of ε-caprolactone, 0.2 mol of p-toluenesulfonic acid monohydrate, and 2.2 mol of pure water were added, and the mixture was stirred at 80°C for 8 hours. Next, the mixture was further stirred for 2 hours while dehydrating under reduced pressure (30 kPa). The remaining propionic acid in the reaction system was then removed by distillation, and the mixture was purified (washed with water 3 times) and dried to obtain dispersant d1 (in the above formula (1), R is an ethyl compound, m is 5, and n is 10).
[0336] [Preparation of Dispersion D1]
[0337] 167 parts by weight of a methanol dispersion of zirconia particles (manufactured by SAKAI CHEMICAL INDUSTRY, grade "SZR-GM", average particle size (D50) based on dynamic light scattering method: approximately 10 nm, zirconia particle concentration: 30 wt%) were mixed with 5 parts by weight of the aforementioned dispersant d1 and 45 parts by weight of phenoxybenzyl acrylate (manufactured by Kyoei Chemicals, trade name "LIGHTACRYLATE POB-A"; hereinafter referred to as "POB-A"). Next, the solvent was removed under reduced pressure using a rotary evaporator to obtain dispersion D1, which is a dispersion of zirconia particles. Dispersion D1 contains zirconia particles / dispersant d1 / POB-A in a weight ratio of 50 / 5 / 45.
[0338] <Preparation of Dispersion D2>
[0339] Synthesis of dispersant d2
[0340] 415 g (1 mol) of tristyrene phenol and 1 g (0.018 mol) of potassium hydroxide were added to an autoclave and mixed uniformly until the reaction system reached 130 °C. Then, 352 g (8 mol) of ethylene oxide (EO) was added dropwise. After the addition was complete, the pressure was maintained at 0.1 MPa at 130 °C for 1 hour to obtain the EO 8-molar adduct of tristyrene phenol. Next, 767 g (1 mol) of the obtained EO 8-molar adduct of tristyrene phenol and 152 g (1.3 mol) of sodium monochloroacetate were added to a reactor and stirred until homogeneous. The reaction system was then brought to 60 °C, 52 g of sodium hydroxide was added, and the temperature was raised to 80 °C for 3 hours. After aging, the mixture was cooled to 50 °C, and 117 g (1.2 mol) of 98% sulfuric acid was added dropwise at the same temperature to obtain a white suspension. The suspension was washed with distilled water, and the solvent was removed by vacuum distillation to obtain dispersant d2.
[0341] A mixture of 100 parts by weight of a methanol dispersion of zirconia particles (manufactured by SAKAI CHEMICAL INDUSTRY, grade "SZR-M", average particle size (D50) based on dynamic light scattering: 3 nm, zirconia particle concentration: 30 wt%), and 1.5 parts by weight of the aforementioned dispersant d2 and 28.5 parts by weight of POB-A were added and mixed. Next, the solvent was removed under reduced pressure using a rotary evaporator to obtain dispersion D2, which is a dispersion of zirconia particles. Dispersion D2 contains zirconia particles / dispersant d2 / POB-A at a weight ratio of 50 / 2.5 / 47.5.
[0342] <Example 1: Added to an adhesive composition containing inorganic particles>
[0343] (Example 1)
[0344] Relative to 100 parts by weight of dispersion D1, 10 parts by weight of polymer B1, 0.05 parts by weight of 1,2-diphenylethane-1-one (manufactured by IGM Resins, trade name "Omnirad 651") as a photopolymerization initiator, 0.05 parts by weight of 1-hydroxycyclohexylphenyl ketone (manufactured by IGM Resins, trade name "Omnirad 184"), 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, 0.3 parts by weight of 3-epoxypropoxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicones, trade name "KBM-403") as a silane coupling agent, and 0.05 parts by weight of 1,9-nonanediol diacrylate (NDDA) as a crosslinking agent were mixed. Thus, the adhesive composition of Example 1 was obtained.
[0345] (Examples 2-13 and Comparative Examples 1-2)
[0346] The types of dispersions, polymer B, and polymer B content were changed as shown in Table 3. Otherwise, the adhesive compositions of Examples 2-13 and Comparative Examples 1-2 were obtained by the same method as in Example 1.
[0347] (Refer to Example 1)
[0348] Unmixed polymer B, except that, the adhesive composition of Reference Example 1 was obtained in the same manner as the adhesive composition of Example 1.
[0349] <Evaluation>
[0350] Using the adhesive compositions of Examples 1-13, Comparative Examples 1-2 and Reference Example 1, an evaluation adhesive sheet was prepared by the following method.
[0351] [Making of the peelable liner]
[0352] A silicone-based release agent composition was prepared by mixing 30 parts by weight of an addition-reaction curable silicone (containing LTC761 with hexenyl polysiloxane, 30% toluene solution, manufactured by Toray Dow Corning), 0.9 parts by weight of a release control agent (containing unreactive silicone resin BY24-850, manufactured by Toray Dow Corning), 2 parts by weight of a curing catalyst (containing platinum catalyst SRX212, manufactured by Toray Dow Corning), and a toluene / hexane mixed solvent (volume ratio 1:1) as a diluent. The concentration of the silicone solid component in the release agent composition was 1.0% by weight. Next, the release agent composition was coated onto one side of a substrate (Lumirror XD500P polyester film, 75 μm thick) using a wire rod, and heated at 130°C for 1 minute to produce a release liner with a release layer (60 nm thick) on one side.
[0353] [Making the Adhesive Sheet]
[0354] An adhesive composition was applied to one side of a substrate sheet (PET separator, made of Mitsubishi resin, MRF38) using an applicator to form a coating layer. Next, the aforementioned release liner was placed on the formed coating layer to obtain the first laminate. The release liner was configured to allow the release layer to contact the coating layer.
[0355] Next, from one side of the substrate sheet of the first laminate, an illuminance of 9mW / cm² is applied. 2 And cumulative light intensity 714 mJ / cm 2 The substrate was irradiated with ultraviolet light for 20 seconds. An LED was used as the light source. The peak wavelength of the irradiated light was 340 nm. This caused the coating layer to photocur, resulting in an adhesive sheet (20 μm thick) sandwiched between the substrate sheet and a release liner. It should be noted that the illuminance was measured using an illuminance meter (TOPCON TECHNOHOUSE, UD-T3040T2) near the incident surface of the ultraviolet light on the substrate sheet.
[0356] Then, following the above operation, illuminance of 18 mW / cm² is applied from one side of the substrate sheet in the first laminate. 2 And cumulative light intensity 667mJ / cm 2 The substrate was exposed to ultraviolet light for several seconds. A metal halide lamp was used as the light source. This process removed any uncured monomers and unreacted initiators remaining in the adhesive sheet. It should be noted that the illuminance was measured using an illuminance meter (TOPCON TECHNOHOUSE, U0-T36T2) near the incident surface of the ultraviolet light on the substrate sheet.
[0357] [Evaluation of Refractive Index]
[0358] For each of the fabricated adhesive sheets, the refractive index of the surface exposed by peeling off the release liner was measured using a prism coupler (Metricon, model "2010M") in critical angle mode at a measurement temperature of 25°C and a measurement wavelength of 594 nm.
[0359] [Haze Level Evaluation]
[0360] For each of the manufactured adhesive sheets, an alkali-free glass plate (thickness 0.7~0.8mm, total light transmittance 92%, chromaticity) is bonded to each exposed surface after peeling off the substrate sheet and release liner. A test piece was obtained by clamping the adhesive sheet between two alkali-free glass plates (0.20). After being placed in an environment of 23°C and 50%RH for 30 minutes, the test piece was placed in a pressure degassing apparatus (autoclave) and subjected to autoclaving treatment at 50°C and 0.5MPa for 30 minutes. Next, it was placed in an atmosphere of 23°C and 50%RH for 24 hours. Finally, the haze of the test piece was measured using a spectrophotometer (Murakami Color Technology Research Institute, HSP-150vis) in a measurement environment of 23°C.
[0361] [Color] [Evaluation]
[0362] For each of the manufactured adhesive sheets, an alkali-free glass plate (thickness 0.7~0.8mm, total light transmittance 92%, chromaticity) is bonded to each exposed surface after peeling off the substrate sheet and release liner. A test piece was obtained by clamping an adhesive sheet between two alkali-free glass plates (0.20). After being placed in an environment of 23°C and 50%RH for 30 minutes, the test piece was subjected to a pressure degassing device (autoclave) and autoclaved at 50°C and 0.5MPa for 30 minutes. Next, it was placed in an atmosphere of 23°C and 50%RH for 24 hours. Then, the transmittance of the test piece for light with wavelengths from 300nm to 800nm was measured using a UV-Vis-NIR spectrophotometer (Hitachi High-Tech, UH4150) at 23°C. The chromaticity was calculated using a color calculation program (Hitachi High-Tech, UV Solutions) based on the obtained spectral data. The absolute value. It should be noted that the above chromaticity... The values are based on reference data (blank data) measured in the measurement chamber of the UV-Vis-NIR spectrophotometer without a sample.
[0363] [Evaluation of Adhesion Strength]
[0364] In a testing environment of 23°C and 50%RH, the release liner was peeled off from each of the prepared adhesive sheets and laminated with a polyethylene terephthalate film (50 μm thick) to form the liner. The resulting laminate was cut into strips measuring 100 mm x 25 mm to serve as test pieces. The substrate sheet was peeled off from the test piece and laminated onto alkali-free glass (Corning, trade name "EG-XG", 0.7 mm thick), and pressed together by a 2 kg roller once.
[0365] After being placed in the aforementioned environment for 30 minutes, the test piece was placed in a pressure degassing apparatus (autoclave) and subjected to autoclaving treatment at 50°C and 0.5 MPa for 30 minutes. Next, it was placed in an atmosphere of 23°C and 50% RH for 24 hours. Then, using a universal tensile and compression testing machine (Shimadzu Autograph SHIMAZUAGX-V 50N), the test piece was peeled from the alkali-free glass at a peel speed of 300 mm / min and a peel angle of 180°. The force necessary to peel the test piece from the alkali-free glass (peel strength) was then determined as the adhesive force.
[0366] [Refractive index difference between polymer B and the base composition]
[0367] The refractive index of the adhesive sheet formed from the adhesive composition of Reference Example 1 was used as the "refractive index of the base composition". The refractive index difference between the refractive index of polymer B and the refractive index of the base composition was determined for each adhesive sheet of Examples 1 to 13 and Comparative Examples 1 to 2.
[0368] The evaluation results are shown in Table 3.
[0369]
[0370] The abbreviations in Table 3 are as follows.
[0371] POB-A: Phenoxybenzyl acrylate (manufactured by Kyoei Chemicals, trade name "LIGHT ACRYLATE POB-A")
[0372] <Example 2 of adding to an adhesive composition containing inorganic particles>
[0373] (Example 14)
[0374] A mixture containing zirconium oxide particles, dispersant d1, POB-A and 4-hydroxybutyl acrylate (4HBA) was obtained relative to dispersion D1 mixed with phenoxybenzyl acrylate (POB-A) and 4-hydroxybutyl acrylate (4HBA), as shown in Table 4. Relative to 100 parts by weight of the mixture, 10 parts by weight of polymer B11, 0.6 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins, trade name "Omnirad 819") as a photopolymerization initiator, 2.5 parts by weight of TINUVIN384-2 (manufactured by BASF) as UVA, 0.5 parts by weight of Irganox1010 (manufactured by BASF) as an antioxidant, 0.5 parts by weight of 3-epoxypropoxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicones, trade name "KBM-403") as a silane coupling agent, and 0.03 parts by weight of 1,9-nonanediol diacrylate (NDDA) as a crosslinking agent were mixed. Thus, the adhesive composition of Example 14 was obtained.
[0375] (Examples 15-20)
[0376] The composition of the mixture, the types of additives, and the content of additives were changed as shown in Table 4. Otherwise, the adhesive compositions of Examples 15-20 were obtained by the same method as in Example 14.
[0377] (See Example 2 for reference)
[0378] Unmixed polymer B, except that the adhesive composition of Reference Example 2 was obtained in the same manner as the adhesive composition of Example 14.
[0379] <Evaluation>
[0380] Evaluation adhesive sheets were prepared using the adhesive compositions of Examples 14-20 and Reference Example 2 by the following method. Furthermore, the adhesive sheets were used to test adhesive strength, refractive index, haze, and color using the same method as in Example 1. Evaluation.
[0381] An adhesive composition was applied to one side of a substrate sheet (PET separator, made of Mitsubishi resin, MRF38) using an applicator to form a coating layer. Next, the aforementioned release liner was placed on the formed coating layer to obtain the first laminate. The release liner was configured to allow the release layer to contact the coating layer.
[0382] Next, from one side of the substrate sheet of the first laminate, an illuminance of 9mW / cm² is applied. 2 And cumulative light intensity 1467mJ / cm 2The conditions for 2 seconds were met with ultraviolet light from a black light source. Simultaneously, illuminance of 9 mW / cm² was applied from one side of the peeling liner of the first layer. 2 And cumulative light intensity 714 mJ / cm 2 Light from the LED (peak wavelength 340 nm) was applied for 2 seconds. This caused the coating layer to photocur, resulting in an adhesive sheet (50 μm thick) sandwiched between the substrate sheet and the release liner. It should be noted that the illuminance of the ultraviolet light from the black light source was measured using an illuminance meter (TOPCON TECHNOHOUSE, U0-T36T2) near the ultraviolet incident surface of the substrate sheet. Additionally, the illuminance of the light from the LED was measured using an illuminance meter (TOPCON TECHNOHOUSE, UD-T3040T2) near the ultraviolet incident surface of the release liner.
[0383] Then, following the above operation, illuminance of 18 mW / cm² is applied from one side of the substrate sheet of the first laminate. 2 And cumulative light intensity 667mJ / cm 2 The substrate was exposed to ultraviolet light for several seconds. A metal halide lamp was used as the light source. This process removed any uncured monomers and unreacted initiators remaining in the adhesive sheet. It should be noted that the illuminance was measured using an illuminance meter (TOPCONTECHNOHOUSE, U0-T36T2) near the incident surface of the ultraviolet light on the substrate sheet.
[0384] [Refractive index difference between polymer B and the base composition]
[0385] The refractive index of the adhesive sheet formed from the adhesive composition of Reference Example 2 was used as the "refractive index of the base composition". The refractive index difference between the refractive index of polymer B and the refractive index of the base composition was determined for each adhesive sheet of Examples 14 to 20.
[0386] The evaluation results of each characteristic are shown in Table 5.
[0387]
[0388] The abbreviations in Table 4 are as follows.
[0389] POB-A: Phenoxybenzyl acrylate (manufactured by Kyoei Chemicals, trade name "LIGHT ACRYLATE POB-A")
[0390] 4HBA: 4-Hydroxybutyl acrylate
[0391] Omni.819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins, trade name "Omnirad819")
[0392] Tinuvin384-2: Benzotriazole UVA (manufactured by BASF, trade name "Tinuvin384-2")
[0393] Tinuvin405: Triazine UVA (manufactured by BASF, trade name "Tinuvin405")
[0394] Tinuvin571: Benzotriazole UVA (manufactured by BASF, trade name "Tinuvin571")
[0395] NDDA: 1,9-Nonadiol diacrylate
[0396] Irganox 1010: Pentaerythritol tetra[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate] ester (manufactured by BASF)
[0397] KBM403: 3-Epoxypropoxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicones, trade name "KBM-403")
[0398] <Examples of addition to adhesive compositions that do not contain inorganic particles>
[0399] (Example 21)
[0400] Relative to 100 parts by weight of polymer POB-A, 3 parts by weight of polymer B1, 0.05 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins, trade name "Omnirad 819") and 0.05 parts by weight of 1,2-diphenylethane-1-one (manufactured by IGM Resins, trade name "Omnirad 651") as photopolymerization initiators, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, 0.3 parts by weight of 3-epoxypropoxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicones, trade name "KBM-403") as a silane coupling agent, and 0.020 parts by weight of 1,9-nonanediol diacrylate (NDDA) as a crosslinking agent were mixed. Thus, the adhesive composition of Example 21 was obtained.
[0401] (Refer to Example 3)
[0402] Unmixed polymer B, except that the adhesive composition of Reference Example 3 was obtained in the same manner as the adhesive composition of Example 21.
[0403] The composition of the adhesive compositions of Example 21 and Reference Example 3 is shown in Table 6.
[0404] <Evaluation>
[0405] Using the adhesive compositions of Example 21 and Reference Example 3, evaluation adhesive sheets were prepared in the same manner as in Example 14. Furthermore, using the prepared adhesive sheets, tests were performed on adhesive strength, refractive index, haze, and color using the same method as in Example 1. Evaluation.
[0406] [Refractive index difference between polymer B and the base composition]
[0407] The refractive index of the adhesive sheet formed from the adhesive composition of Reference Example 3 was used as the "refractive index of the base composition". The refractive index difference between the refractive index of polymer B and the refractive index of the base composition was determined for the adhesive sheet of Example 21.
[0408] The evaluation results are shown in Table 7.
[0409]
[0410] The abbreviations in Table 6 are as follows.
[0411] POB-A: Phenoxybenzyl acrylate (manufactured by Kyoei Chemicals, trade name "LIGHT ACRYLATE POB-A")
[0412] Omni.819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins, trade name "Omnirad819")
[0413] Omni.651: 1,2-Diphenylethane-1-one (manufactured by IGM Resins, trade name "Omnirad 651")
[0414] NDDA: 1,9-Nonadiol diacrylate
[0415] Irganox 1010: Pentaerythritol tetra[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate] ester (manufactured by BASF)
[0416] KBM403: 3-Epoxypropoxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicones, trade name "KBM-403")
[0417] According to Tables 1-7, polymer B with a Mw of 1500-30000, a Tg below 30°C, and a refractive index above 1.51 is suitable for manufacturing adhesive sheets with high refractive index and improved adhesion.
[0418] Industrial applicability
[0419] The polymers of the present invention can be used, for example, in photocurable adhesive compositions.
Claims
1. A polymer having a weight-average molecular weight of 1,500 to 30,000, a glass transition temperature below 30°C, and a refractive index of 1.51 or higher.
2. The polymer according to claim 1, wherein, The polymer has a δH value of 5.15 or less. Wherein, δH is the hydrogen bond term of the Hansen solubility parameter (HSP).
3. The polymer according to claim 1, wherein, The colorimetric properties of the polymer are as specified in CIE 1976 L as defined in JIS Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value is expressed as below 1.
1.
4. The polymer according to claim 1, wherein, The weight-average molecular weight of the polymer is 2400-16000.
5. The polymer according to claim 1, wherein, The polymer comprises constituent units derived from monomer b having a double-bonded ring.
6. The polymer according to claim 5, wherein, The double-bonded ring is an aromatic ring.
7. The polymer according to claim 5, wherein, The monomer b has two or more double-bonded rings in its side chain.
8. The polymer according to claim 7, wherein, The monomer b has a structure in which the first double-bonded ring and the second double-bonded ring, which are included in the two or more double-bonded rings, are bonded together by a linking group in the side chain.
9. The polymer according to claim 5, wherein, The monomer b is phenoxybenzyl acrylate.
10. The polymer according to claim 5, wherein, The polymer contains at least 50% by weight of the constituent unit derived from monomer b.
11. A thickener comprising the polymer according to any one of claims 1 to 10.
12. A tackifier comprising a polymer having a weight-average molecular weight of 1500 to 30000. The polymer comprises constituent units derived from monomer b having a double-bonded ring. The monomer b has two or more double-bonded rings in its side chain.
13. A light-curable adhesive composition comprising: Monomer component M; and The polymer according to any one of claims 1 to 10, or the tackifier according to claim 12.
14. An adhesive sheet formed from the adhesive composition of claim 13.
15. An optical laminate comprising: The adhesive sheet as described in claim 14, and Optical film.
16. An image display device comprising the optical laminate of claim 15.
Citation Information
Patent Citations
Draining device, and indoor unit of air conditioner
JP2012013303A
Optical display device having polarizing film
JP2012133303A
Adhesive composition for optical member, optical laminate and surface light source device
JP2017014376A